West Antarctic subglacial geology distinguished by Pb isotopes and Rb–Sr ages in ice-rafted feldspars - Thomas Arney; Claus-Dieter Hillenbrand; Thomas M. Belgrano; J. Andy Milton; Christine S. Siddoway; Gavin L. Foster; Paul A. Wilson; Julia S. Wellner; Steve M. Bohaty (Earth and Planetary Science Letters, 2026)

Nutrition Services in Oncology: A Cross-Sectional Survey of Patient Experiences, Needs, and Gaps in Care - Bailey M. Foster; Melissa F. Miller; Colleen K. Spees; Cynthia A. Thomson; Elaine B. Trujillo; Erica E. Fortune; Lauren Fay; Peter A. Adintori; Renee Stubbins; Jill M. Hamilton-Reeves (Journal of the Academy of Nutrition and Dietetics, 2026)

Bond–slip behaviour and constitutive modelling of screwed-in threaded rods in glulam joints - M. Elzeadani; R.M. Foster (Engineering Structures, 2026)

Retaining fruiting trees in the agricultural matrix is important for bird-mediated seed dispersal in a fragmented forest landscape - Jelaine Lim Gan; Katrin M. Meyer; Marion Pfeifer; Terence Craig Soroño; Erwin Somera Torio; Merlijn van Weerd; Marites Gatan-Balbas; Mark David Foster Shirley (Ecological Modelling, 2026)

Correction: The influence of mouth pressure on the cardiovascular response during inspiratory muscle loading at a constant transdiaphragmatic pressure - Megan L. Lance; Scott F. Thrall; Benjamin P. Thompson; Leah M. Mann; Jou-Chung Chang; Katherine M. Taylor; Nadia M. Navarro Solano; Madison J. Gorsline; Richard J. A. Wilson; Trevor A. Day; Paolo B. Dominelli; Glen E. Foster (European Journal of Applied Physiology, 2026)

Integrated modelling reveals widespread distribution of invasive wild pigs across Australia - Matthew W. Rees; David J. Mitchell; Katherina Ng; Sandra K. Parsons; Kirstin M. Proft; Scott D. Foster; David Peel; Zachary Amir; Tom Bruce; Matthew S. Luskin; Jens G. Froese (Biological Conservation, 2026)

Murine Abdominal Aortic Aneurysm Intraluminal Thrombus Composition and Structure - Cortland H. Johns; Luke E. Schepers; Annabelle M. F. Foist; Ethan P. Foster; Anish Bedi; Niharika Narra; Claudia K. Albrecht; Abigail D. Cox; Craig J. Goergen (Annals of Biomedical Engineering, 2026)
Purpose Many abdominal aortic aneurysm (AAA) patients develop intraluminal thrombus (ILT), but the role of ILT in AAA progression and rupture is poorly understood. Methods To evaluate ILT in AAAs, we induced AAAs in C57Bl6/J mice via surgical application of topical elastase to the abdominal aorta below the renal arteries and administration of β-aminopropionitrile (BAPN) in drinking water. Ultrasound images of these AAAs were collected longitudinally over a period of 56 days to evaluate AAA growth over time. We semi-quantitatively assessed elastin degradation and inflammation from Movat’s pentachrome and H&E-stained samples, respectively. Additionally, we assessed extracellular matrix composition and elastin quality through Movat’s pentachrome stained samples. Results Mice subjected to elastase + BAPN exhibited continuous and significant AAA growth over time. Mice with ILT had more significant expansion over the length of the study ( p Conclusion Understanding the relationship between ILT formation, aortic wall degradation, and inflammation could help refine clinical strategies for monitoring and treating AAAs. These data suggest that work focused on modulating inflammation and ILT formation could offer promising pathways for non-surgical intervention in AAA treatment.

An interactive tool to identify existing evidence and research gaps on agricultural production processes to address heavy metals in foods: developed from a scoping review - Rupal Trivedi; Lauren E. O’Connor; Cassi N. Leta; Trish J. Bosse; Julie S. Davis; Arin A. Balalian; Rachel C. Thoerig; Shailesh M. Advani; Margaret J. Foster; Kyle M. Holland; David D. Baltensperger; Delbert M. Gatlin III; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Constraining environmental controls on the incorporation of Mg, Na and Sr in cultured Globigerina bulloides: implications for biomineralisation and high latitude palaeoceanography - F.E. Sykes; M.M. Ezat; A. Westgård; G.L. Foster; J. Meilland; T.B. Chalk; J.A. Milton; M. Chierici (Geochimica et Cosmochimica Acta, 2026)

Laboratory-grown crust in planktic foraminifera Neogloboquadrina pachyderma; insights into resolving inaccuracies in polar palaeotemperature estimates - Adele Westgård; Mohamed M. Ezat; Freya E. Sykes; Gavin L. Foster; Julie Meilland; Thomas B. Chalk; J. Andy Milton (Geochimica et Cosmochimica Acta, 2026)

Sequestration of chlorine in scapolite during metamorphism and the formation and role of residual bittern brines for mineralized systems in the Mesoproterozoic Belt Supergroup, North America - I.M.T. Rein; J. Hammerli; R.S. Lewis; M. Foster; S. Boroughs (Chemical Geology, 2026)

Dietary nitrate supplementation does not improve resistance exercise performance in resistance-trained women - Sydney N. Brennan; Justin M. Foster; Raymond T. Gerardo; Trevor J. Molnar; Ryan Tran; Christopher B. Sottile; Kyle S. Geppert; Michael Egiazarian; Abigail F. Ballhagen; Money Ghimire; John R. M. Renwick; Lewis A. Gough; et al. (European Journal of Applied Physiology, 2026)

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

The influence of mouth pressure on the cardiovascular response during inspiratory muscle loading at a constant transdiaphragmatic pressure - Megan L. Lance; Scott F. Thrall; Benjamin P. Thompson; Leah M. Mann; Jou-Chung Chang; Katherine M. Taylor; Nadia M. Navarro Solano; Madison J. Gorsline; Richard J. A. Wilson; Trevor A. Day; Paolo B. Dominelli; Glen E. Foster (European Journal of Applied Physiology, 2026)

Individual foraminiferal analysis: A promising tool for high-resolution temperature and pH reconstruction - Zifei Yang; Christopher D. Standish; Rachel M. Brown; Patrick A. Rafter; Malcolm B. Hart; Tali L. Babila; Gavin L. Foster (Chemical Geology, 2026)

Energy-sector footprints, subsequent disturbances and footprint reclamation determine the direction and rate of landbird community trajectories in boreal forests - Tharindu Kalukapuge; Christine M. Godwin; Kenneth R. Foster; James F. Saracco; Erin Bayne (Journal of Environmental Management, 2026)

Ti solubility in biotite at low pressure in metapelitic systems: the Torres del Paine case - Maria M. Ariza-Acero; Lukas P. Baumgartner; C. Tom Foster; Marisa D. Acosta; Jo Moore; Jack Gillespie; Robert Bodner; Guillaume Siron (Contributions to Mineralogy and Petrology, 2026)
The Torres del Paine Intrusive Complex (TPIC) is a shallowly emplaced pluton surrounded by a well-defined contact aureole, providing an ideal setting to test Ti-in-biotite thermometry. We compare existing Ti-in-biotite thermometers with phase petrology constraints and found that they systematically overestimate peak metamorphic temperatures. This discrepancy arises from a significant increase in Ti solubility at low pressures $$(<1$$ kbar). In fact, we demonstrate that a pressure difference of $$\sim 0.25$$ kbar within the aureole leads to an increase of 0.1 a.p.f.u. in Ti content, suggesting that pressure plays a key role in Ti incorporation at these low pressures. At lower pressures, the Ti-oxy substitution becomes saturated, and Ti incorporation is dominated by a Ti-spinel exchange mechanism. Additionally, textural and chemical analyses reveal that composition vary between small domains of a few hundred micrometers, indicating that local compositional heterogeneities significantly influences Ti content in biotite, even when a Ti-oxide and an Al-rich silicate are nearby. Finally, biotite starts growing near to the biotite-in isograd, and keeps on growing, so that its composition does not fully adjust to the peak composition due to the short metamorphic event. These findings highlight that both pressure and temperature influence the Ti content in biotite. The application of Ti-in-biotite thermometry requires careful consideration of equilibrium domains and growth kinetics.

Simulation of recurring defoliation by multiple insects shows lasting consequences for carbon storage in temperate oak forests - Jane R. Foster; Robert M. Scheller; Brian R. Sturtevant; Philip A. Townsend; Brian Miranda; David J. Mladenoff (Forest Ecology and Management, 2026)

Cumulative effects analysis to inform public land management in the United States: key characteristics and legal challenges - Tait K. Rutherford; Tim O. Hammond; Alison C. Foster; Megan A. Gilbert; Travis S. Haby; Richard J. Lehrter; Jennifer K. Meineke; Ella M. Samuel; Sarah K. Carter (Environmental Impact Assessment Review, 2026)

Phenological shifts and increases in voltinism within a moth community over a century of anthropogenic change - Emma M. Foster; Jason J. Dombroskie; Christopher A. Halsch; Thomas H. Q. Powell; Eliza M. Grames (Ecology, 2026)
In temperate ecosystems, warming temperatures can advance spring phenology, extend autumn phenology, disrupt dormancy regulation, result in phenological mismatch across taxa, and even lead to increases in the number of generations per year (i.e., increases in voltinism). Much of what we know about the impacts of global change on species phenology and voltinism comes from recent decades; however, anthropogenic warming began centuries ago. Using light trap datasets from 1889–1892 and 1919–1922, alongside contemporary records, we document long‐term changes in phenology and voltinism for 78 moth species, and changes in occurrence for 169 species, in New York, USA. From 1919–1922 to 2019–2024, we found an advance in spring phenology by 0.55 days per decade and an extension of the end of the flight period by 1.18 days per decade. This shift was largely driven by bi‐ and multivoltine species, which have added generations extending the end of their flight period by 1.58 days per decade compared to an extension of only 0.49 days per decade for univoltine species. We also document the apparent disappearance of 13 species from the region from 1889 to present, whose ranges now tend to be farther north and at higher elevations, possibly due to global change. As this region becomes warmer and wetter with ongoing climate change, more species may extend their active period or add more generations per year, with the potential for rapid adaptation and consequences for ecosystem function as some insect herbivores become more abundant.

Morrittospora corbiculae n. gen. n. sp., a microsporidian parasite infecting the invasive Asian clam Corbicula fluminea from the River Thames, London - Rachel Foster; Kelly S. Bateman; Paul F. Clark; Matthew J. Green; Chantelle Hooper; Stuart H. Ross; Paul Stebbing; Georgia M. Ward; David Bass (Journal of Invertebrate Pathology, 2026)

Arsenic, cadmium, lead, mercury, and PFAS exposure during pregnancy or lactation and respective concentrations in human milk: Systematic review - Lauren E. O'Connor; Cassi N. Uffelman; Rachel C. Thoerig; Arin A. Balalian; Rupal Trivedi; Trish Bosse; Margaret J. Foster; Kyle M. Holland; Kathryn G. Dewey; Mandy M. Fisher; Aubrey L. Galusha; Carin A. Huset; et al. (Environmental Research, 2026)

Genomic Architecture of Inbreeding Depression Associated With Hatching Failure in an Endangered Parrot - Yasmin Foster; Stefanie Grosser; Brodie J. Foster; Nicolas Dussex; Aimee Stubbs; Ludovic Dutoit; Theo Atkinson; Fiona Robertson; Ken G. Dodds; Rudiger Brauning; Jeanne M. E. Jacobs; John C. McEwan; et al. (Molecular Ecology, 2026)
Conservation management of endangered species increasingly relies on genomic approaches to understand how long‐term small population sizes affect the fitness of extant individuals. However, despite the growing investment in genomic resources by conservation programmes, the impact that sequencing methods have on the ability to detect inbreeding‐related phenomena has been largely overlooked. Here, we compare the use of whole‐genome and reduced‐representation sequencing approaches in 148 individuals of the critically endangered parrot, the kākāpō ( Strigops habroptilus ), to assess inbreeding and its effects on female reproductive success. We explore how sequencing choice influences the identification of long stretches of homozygosity across the genome (runs of homozygosity, ROH), and compare the conservation implications of the results produced by each method. Both whole‐genome and reduced‐representation sequencing approaches provided comparable estimates of genome‐wide inbreeding ( F ROH ) and revealed consistent effects on egg hatching success, suggesting that reduced‐representation sequencing is capable of detecting inbreeding depression in wild populations under certain conditions. Whole‐genome sequencing enabled chromosome‐level inbreeding analyses, which revealed no strong evidence of chromosome‐specific effects beyond the genome‐wide signal. These results suggest that inbreeding depression in kākāpō reflects small effects across many chromosomes rather than strong effects on only a few, and that the primary benefit of whole‐genome sequencing lies in improving the precision of genome‐wide inbreeding estimates rather than identifying chromosome‐specific effects. Our findings highlight the distinct benefits of each sequencing approach in conservation, particularly within the context of resource limitations.

On-site sanitation systems and fecal contamination in shallow groundwater in urban Indonesia: assessing influence of distance and rainfall variables - Gita L. Putri; Akna M. Ilmi; Rahayu Handayani; Dadang Iskandar; Cindy R. Priadi; Juliet Willetts; Tim Foster (Water Research, 2025)

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Challenges and Strategic Recommendations for Enhancing Quantification and Projection of Forest Carbon Dynamics - Holly L. Munro; Christopher W. Woodall; William R. L. Anderegg; Jeff W. Atkins; Colin M. Beier; Bronson P. Bullock; Kendall DeLyser; David D. Diaz; Bianca N.I. Eskelson; Margaret E. K. Evans; John D. Foppert; Bryan C. Foster; et al. (Journal of Forestry, 2025)

Global Patterns and Drivers of Seagrass Biomass, Net Primary Production and Meadow Structure - Nicole R. Foster; Enric Gomis; Diana I. Montemayor; Simone Strydom; Miguel Angel Mateo; Eduard Serrano; Aurora M. Ricart; Martin Dahl; Ines Mazarrasa; Paulina Cisternas; Harry Whiteley; Elliott J. Bates; et al. (Journal of Biogeography, 2025)
Aim We decipher global patterns in seagrass growth and structure to advance seagrass science, facilitate multidisciplinary research, and promote effective management strategies and policy development for seagrass habitats. Location: Global. Time period: 1975 to 2024. Major taxa studied: Seagrasses—marine angiosperms. Methods A global data set on seagrass total biomass, total net primary productivity (NPP), shoot density, and percent cover was compiled across 11 genera. We tested how these variables change across seagrass genera, life‐history strategy, and geographic location; and then modelled the environmental drivers (temperature, nutrients, light availability) of the patterns observed. Results The mean (±SE) total biomass of seagrasses globally was estimated at 340 ± 10 g DW m −2 and total NPP was estimated at 5.4 ± 0.4 g DW m −2 d −1 . Mean shoot density across all genera was 1,780 ± 67 shoots m −2 and percent cover was 42% ± 1%. Persistent genera showed the highest total biomass followed by opportunistic then colonising genera, whereas shoot density was higher for colonising than persistent, which had the highest percent cover. Latitudinal and bioregional patterns were identified for some genera and were mostly driven by genus‐specific traits, followed by localised environmental factors. Main Conclusions Trends in seagrass meadow ecology were largely influenced by seagrass genera and their life‐history strategy, with localised environmental factors, such as temperature and nutrients, also playing a role. Global estimates of seagrass biomass and NPP were 2‐times higher than previously reported. Seagrass life‐history strategies modulate the trade‐offs between NPP and biomass to thrive in specific habitats. This study provides the most updated global synthesis of patterns in seagrass growth and structure.

Understanding psilocybin mushrooms and aiding in setting standards for a burgeoning industry in Jamaica - Rupika Delgoda; Kimberley Foster; Isaac Morrison; Marshall Tyler; William Irvine; Lavonne Wilson; Babumon M. Thankappan; Shemar Daniel (Phytochemistry Letters, 2025)

Parental Weaning Style Intent vs Reality: What Factors Affect If a Parent Intends and Completes Baby-led Weaning, Mixed Weaning, or Traditional Weaning - K. Whitley; D. Jacobvitz; S. Foster; L. Hernandez; M. Burgermaster; S. Dube; M. Abrego; A. Ramos-Gonzalez; M. Bradley; K. Ornelas; L. Sandoval-Mejia; I. Martinez; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

GDF-15 - Implications for Bladder Cancer Care and Symptom Control - B. Foster; R. Vargas; P. Srinivasan; D. Koestler; M. Bechtel; J. Holzbeierlein; M. Fisch; N. Henry; J. Unger; J. Hamilton-Reeves (Journal of the Academy of Nutrition and Dietetics, 2025)

Descriptive analysis of whole blood concentrations of toxic, essential, and trace elements in adult females from the MIREC-ENDO study - Sara Packull-McCormick; Jillian Ashley-Martin; Michèle Bouchard; Mandy Fisher; Tye E. Arbuckle; Kristin Macey; Maryse Bouchard; Warren Foster; Michael M. Borghese (Environmental Research, 2025)

The effect of dietary nitrate supplementation on resistance exercise performance: A dose–response investigation - Rachel Tan; Isabella G. Lincoln; Keonabelle K. Paniagua; Justin M. Foster; Lauren E. Wideen; Raymond T. Gerardo; Nathan J. Ornelas; Isaac Tchaprazian; Jeffrey Li; Michael Egiazarian; Samantha N. Rowland; Stephen J. Bailey; et al. (European Journal of Applied Physiology, 2025)
Dietary nitrate (NO 3 − ) can enhance skeletal muscle contractile function and explosive-type exercise by modulating type II muscle fibers; however, limited attention has been directed at exploring the optimal dosing guidelines and potential performance-enhancing effects of NO 3 − supplementation during resistance-type exercise. The purpose of our investigation was to examine potential dose–response effects of concentrated NO 3 − -rich beetroot juice on neuromuscular performance during resistance exercise. Eighteen resistance-trained men were assigned in a double-blind, randomized, crossover design, to four conditions to consume beetroot juice containing: negligible NO 3 − (PL); ~ 6 mmol NO 3 − (BR-LOW); ~ 12 mmol NO 3 − (BR-MOD); and ~ 24 mmol NO 3 − (BR-HIGH). Participants completed 1 set of vertical countermovement jumps (CMJ), 2 sets × 3 repetitions of barbell back squats, and 2 sets × 3 repetitions of barbell bench press 2.5 h post-supplementation. Plasma [NO 3 − ] increased in a dose-dependent manner ( P < 0.01). Plasma [nitrite] ([NO 2 − ]) increased in all BR conditions compared to PL ( P < 0.05), such that BR-MOD vs. BR-LOW ( P < 0.01) and BR-LOW vs. PL ( P < 0.01), but BR-HIGH was not different compared to BR-MOD ( P > 0.05). Performance was not different between conditions in CMJ, 50% one-repetition maximum (1RM) and 75%1RM back squats, or 50%1RM and 75%1RM bench press ( P > 0.05). The change in plasma [NO 2 − ] was significantly correlated with peak power ( r = − 0.65, P = 0.003), mean power ( r = − 0.52, P = 0.03), and mean velocity ( r = − 0.48, P = 0.04) during 50%1RM back squats following BR-LOW vs. PL but not in other conditions ( P > 0.05). This study indicates that dietary NO 3 − does not impact resistance exercise performance at any of the doses assessed in the current study.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Effects of polystyrene nanoplastics on the female reproductive system in mice: Implications for ovarian function and follicular development - Mahsa Gholiof; Jocelyn M. Wessels; Warren G. Foster; Victoria Turpin; Mathew Leonardi (Reproductive Toxicology, 2025)

Societal value of seagrass from historical to contemporary perspectives - Nicole R. Foster; Eugenia T. Apostolaki; Katelyn DiBenedetto; Carlos M. Duarte; David Gregory; Karina Inostroza; Dorte Krause-Jensen; Benjamin L. H. Jones; Eduard Serrano; Rym Zakhama-Sraieb; Oscar Serrano (Ambio, 2025)
Seagrasses have been entwined with human culture for millennia, constituting a natural resource that has supported humanity throughout this history. Understanding the societal value of seagrass fosters appreciation of these ecosystems, encouraging conservation and restoration actions to counteract historic and predicted losses. This study overviews the plethora of seagrass use in human history, ranging from spiritual and ceremonial roles, direct and indirect food resources, medicines and raw materials, dating back more than 180 000 years. While many past uses have been abandoned in modern societies, others have persisted or are being rediscovered, and new applications are emerging. As these uses of seagrasses depend on harvesting, we also underscore the need for sustainable practices to (re)generate positive interactions between seagrasses and society. Our review contributes to revalue seagrass societal ecosystem services, highlighting ancient and more recent human and seagrass relationships to incentivize conservation and restoration actions.

Purification of uranium tetrafluoride using ammonium bifluoride - Kyle R. Foster; Juliano Schorne-Pinto; Ronald E. Booth; Annabelle Husek; Mina Aziziha; Hunter B. Tisdale; Bernie W.N. Fitzpatrick; Hans-Conrad zur Loye; Markus H.A. Piro; Theodore M. Besmann (Journal of Fluorine Chemistry, 2025)

Understanding Wave Attenuation Across Marshes: Insights from Numerical Modeling - Madeline R. Foster-Martinez; Ioannis Y. Georgiou; Duncan M. FitzGerald; Zoe J. Hughes; Alyssa Novak; Md Mohiuddin Sakib (Journal of Marine Science and Engineering, 2025)
Marsh vegetation dampens wave energy, providing protection to coastal communities from storms. A new modeling framework was applied to study wave height evolution over the saltmarsh bordering Newbury, MA. A regional Delft3D hydrodynamic model generated wind driver waves in the open water portions of the study area, which were then one-way coupled with an analytical model, the Marsh Transect Wave Attenuation (MTWA) model, which tracked wave evolution along select transects throughout the marsh. Field observations of vegetation and wave height evolution were used to calibrate MTWA. Seven scenarios were run covering a range of possible future management and environmental conditions, in addition to projected sea level rise. Results underscore the importance of vegetation and elevation to wave attenuation.

Legacy, alternative, and precursor PFAS and associations with lipids and liver function biomarkers: results from a cross-sectional analysis of adult females in the MIREC-ENDO study - Michael M. Borghese; Jingxue Feng; Chun Lei Liang; Natasha Kienapple; Katherine E. Manz; Mandy Fisher; Tye E. Arbuckle; Ella Atlas; Joseph M. Braun; Maryse F. Bouchard; Warren Foster; Jillian Ashley-Martin (International Journal of Hygiene and Environmental Health, 2025)

Coverage matters: identifying and mitigating sampling frame issues in recreational fishing surveys - S. M. Taylor; A. de Groote; K. Hyder; J. H. Vølstad; B. W. Hartill; J. Foster; R. Andrews; K. L. Ryan (Reviews in Fish Biology and Fisheries, 2025)
Surveys play an integral part in monitoring and maintaining sustainable recreational fisheries. For any probabilistic survey, the selection of a sampling frame (e.g., list of individuals or fishers) is an important decision because it influences the ability to provide unbiased estimates of recreational catch and effort. Undercoverage occurs when units of the target population (i.e., the population of interest) are missing from the frame population. This error can undermine the reliability of research advice generated from survey estimates. In this review, we: (i) define six sampling frame configurations that are commonly applied in probabilistic recreational fishing surveys; (ii) synthesise how coverage errors associated with each configuration have been addressed for marine recreational fisheries globally; (iii) outline approaches to identify and correct for coverage errors; and (iv) recommend how to future-proof coverage issues. In our six case studies, multiple types of undercoverage were identified and addressed to varying extents, depending on the characteristics of each fishery and type of sampling frame used. Generalised list frames (particularly phone lists) are arguably the most prone to undercoverage error. To assist in future-proofing surveys, we recommend: (1) considering coverage error during survey planning; (2) designing pilot surveys or scheduling concurrent surveys to evaluate and/or correct for potential bias; (3) recognising that coverage error often changes through time; (4) using technological or multi-frame approaches to mitigate coverage error; (5) considering model-based survey tools to correct for undercoverage; and (6) documenting the sampling frame and potential sources of coverage error in publications. These recommendations extend to inland recreational fisheries, commercial fishing surveys and fisheries-independent surveys. Graphical abstract

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

When can we detect lianas from space? Toward a mechanistic understanding of liana‐infested forest optics - Marco D. Visser; Matteo Detto; Félicien Meunier; Jin Wu; Jane R. Foster; David C. Marvin; Peter M. van Bodegom; Boris Bongalov; Matheus Henrique Nunes; David Coomes; Hans Verbeeck; J. Antonio Guzmán Q; et al. (Ecology, 2025)
Lianas, woody vines acting as structural parasites of trees, have profound effects on the composition and structure of tropical forests, impacting tree growth, mortality, and forest succession. Remote sensing could offer a powerful tool for quantifying the scale of liana infestation, provided the availability of robust detection methods. We analyze the consistency and global geographic specificity of spectral signals—reflectance across wavelengths—from liana‐infested tree crowns and forest stands, examining the underlying mechanisms of these signals. We compiled a uniquely comprehensive database, including leaf reflectance spectra from 5424 leaves, fine‐scale airborne reflectance data from 999 liana‐infested canopies, and coarse‐scale satellite reflectance data covering 775 ha of liana‐infested forest stands. To unravel the mechanisms of the liana spectral signal, we applied mechanistic radiative transfer models across scales, establishing a synthesis of the relative importance of different mechanisms, which we corroborate with field data on liana leaf chemistry and canopy structure. We find a consistent liana spectral signal at canopy and stand scales across globally distributed sites. This signature mainly arises at the canopy level due to direct effects of more horizontal leaf angles, resulting in a larger projected leaf area, and indirect effects from increased light scattering in the near and short‐wave infrared regions, linked to lianas' less costly leaf construction compared with trees on average. The existence of a consistent global spectral signal for lianas suggests that large‐scale quantification of liana infestation is feasible. However, because the traits responsible for the liana canopy‐reflectance signal are not exclusive to lianas, accurate large‐scale detection requires rigorously validated remote sensing methods. Our models highlight challenges in automated detection, such as potential misidentification due to leaf phenology, tree life history, topography, and climate, especially where the scale of liana infestation is less than a single remote sensing pixel. The observed cross‐site patterns also prompt ecological questions about lianas' adaptive similarities in optical traits across environments, indicating possible convergent evolution due to shared constraints on leaf biochemical and structural traits.

The influence of mucilage-rich flours from diverse Australian Plantago species on the pasting, storage, and gluten-free breadmaking properties of rice flour - James M. Cowley; Yi Ren; Lucija Štrkalj; Tim J. Foster; Rachel A. Burton (Food Hydrocolloids, 2025)

Identifying Priority Science Information Needs for Managing Public Lands - Sarah K. Carter; Travis S. Haby; Ella M. Samuel; Alison C. Foster; Jennifer K. Meineke; Laine E. McCall; Malia K. Burton; Christopher T. Domschke; Leigh D. Espy; Megan A. Gilbert (Environmental Management, 2025)

International Consortium to Classify Ageing-related Pathologies (ICCARP) senescence definitions: achieving international consensus - Emma Short; Robert T. R. Huckstepp; Kambiz Alavian; Winfried M. K. Amoaku; Thomas M. Barber; Edwin J. R. van Beek; Emyr Benbow; Sunil Bhandari; Phillip Bloom; Carlo Cota; Paul Chazot; Gary Christopher; et al. (GeroScience, 2025)

Re-examination of archived materials reveals infection of zebra mussels Dreissena polymorpha in UK waters with the parasite Haplosporidium raabei - Rachel Foster; Jasmine E. Hunt; Kelly S. Bateman; Matthew J. Green; William Ball; Matt Longshaw; Laura Heath; Paul Stebbing; Georgia M. Ward (Biological Invasions, 2025)

Physiological and morphological scaling enables gigantism in pelagic protists - Janet E. Burke; Leanne E. Elder; Amy E. Maas; Daniel E. Gaskell; Elizabeth G. Clark; Allison Y. Hsiang; Gavin L. Foster; Pincelli M. Hull (Limnology and Oceanography, 2025)
Planktonic foraminifera are pelagic protists frequently used to study paleoenvironmental change. Many planktonic foraminifera, like other taxa in Rhizaria, reach gigantic proportions relative to other pelagic protists (> 600 μ m), placing them in a size class dominated by metazoans. Here, we combine new and existing respiration rate measurements, micro‐CT scans, and test size measurements to investigate allometric scaling of metabolic rates, relative biomass density, and mixotrophy in contributing to the ability of planktonic foraminifera to reach large sizes. Respiration rate increases with foraminiferal biovolume with a slope of 0.51 ± 0.18. This allometric scaling slope is lower than those reported in other plankton. Further, the basal respiration rates for planktonic foraminifera exceed those of other organisms in their size class when probable biomass, rather than test volume, is considered. Using the allometric regression on a published database of modern planktonic foraminifera from the Atlantic Ocean, we estimate that gigantic individuals account for 15.3–26.1% of foraminiferal community respiration in temperate and tropical/subtropical latitudes, despite making up only 4.5–8.3% of individuals. We hypothesize that shallow scaling of test size with metabolism and of test size to actual biomass is the key factor allowing for gigantism in planktonic foraminifera. Having a large test and broadcasting rhizopodial networks increases the functional volume of the organism, allowing higher passive prey encounter rates to support the elevated metabolic rates in planktonic foraminifera. Mixotrophy may act as a mitigating factor for metabolic challenges at low latitudes, accounting for the presence of large populations of giant, predominately mixotrophic Rhizarians in these assemblages.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Urban wall lizards are resilient to high levels of blood lead - Maya M. Moore; Emma G. Foster; Ali Amer; Logan Fraire; Alyssa Head; Annelise Blanchette; Shala J. Hankison; Alex R. Gunderson; Eric J. Gangloff (Environmental Research, 2025)

Resistance- and endurance-trained young men display comparable carotid artery strain parameters that are superior to untrained men - Ian Hornby-Foster; Cory T. Richards; Aimee L. Drane; Freya M. Lodge; Michael Stembridge; Rachel N. Lord; Hannah Davey; Zaheer Yousef; Christopher J. A. Pugh (European Journal of Applied Physiology, 2025)
Purpose Central arterial stiffness, a predictor of cardiovascular risk, attenuates with endurance-exercise in ageing populations. However, in young individuals, this effect is inconsistent and emerging evidence suggests resistance-exercise may increase arterial stiffness. Two-dimensional (2D)-Strain imaging of the common carotid artery (CCA) is more sensitive at detecting endurance-training induced alterations in CCA stiffness than conventional methods, but has not been used to examine CCA stiffness in young resistance-trained individuals. Therefore, we compared CCA 2D-Strain parameters at rest, during acute exercise and recovery between resistance-trained, endurance-trained, and untrained young men. Methods Short-axis CCA ultrasound images were obtained from 12 endurance-trained [27yrs (95%CI; 24–29)], 14 resistance-trained [24yrs (23–26)] and 12 untrained [23yrs (22–24] men at rest, during isometric handgrip (IHG) exercise and recovery. 2D-Strain analysis quantified CCA peak circumferential strain (PCS) and systolic (S-SR) and diastolic (D-SR) strain rates. Conventional stiffness indices included aortic pulse-wave velocity, CCA β -stiffness ( β 1 ) and Petersons elastic modulus ( E p ). Results Resting conventional stiffness indices were not different between groups ( P > 0.05). Resting PCS and S-SR were comparable between resistance- [11.6% (10.6–12.5) and 1.46 s −1 (1.37–1.55), respectively] and endurance-trained [11.4% (10.7–12.2) and 1.5 s −1 (1.38–1.62)] men and superior to untrained men [9.5% (9.19–9.9); P < 0.004 and 1.24 s −1 (1.17 – 1.31); P < 0.018)]. Both trained groups displayed comparable reductions in PCS and S-SR during IHG, which returned to resting values during recovery ( P < 0.001), whereas these parameters remained unchanged in untrained men. D-SR decreased during IHG in all groups ( P < 0.001), but to a lesser extent in endurance-trained men ( P < 0.023), whereas β 1 and E p increased to a similar magnitude in all groups and returned to resting values during recovery ( P < 0.001). Conclusion Resistance- and endurance-trained men display comparable CCA 2D-Strain parameters that are superior to untrained men, which contends previous reports that resistance-training increases CCA stiffness.

Species Sensitivity Distribution (SSD) profiles towards λ-cyhalothrin for key ecosystem service provider (ESP) species across five European countries representing different pedoclimatic zones - José M. Blanco-Moreno; Berta Caballero-López; Samantha M. Cook; Stephen P. Foster; Danuta Frydryszak; Ryszard Laskowski; Patricia Ortega-Ramos; Mykola Rasko; Pauline Reichardt; José Paulo Sousa; Grzegorz Sowa; Renata Śliwińska-Grochot; et al. (Science of The Total Environment, 2024)

Pedigree tracing to determine the origins of the modern Palomino Horse Breeders of America stock-type horse - B. Pepper; E. North; M. Foster; J. Culwell; M.C. Nicodemus; C. Cavinder; K. Harvey; T. Williams (Journal of Equine Veterinary Science, 2024)

2D geochemical imaging of biogenic marine carbonates using LA-TOF-ICP-MS at 1 and 2 μm pixel resolution - Christopher D. Standish; J. Andy Milton; Tessa M. Page; Rachel M. Brown; David Douglas; Bence Paul; Lukas Schlatt; Gavin L. Foster (Chemical Geology, 2024)

The rheology of rhyolite magma from the IDDP-1 borehole and Hrafntinnuhryggur (Krafla, Iceland) with implications for geothermal drilling - Fabian B. Wadsworth; Jérémie Vasseur; Yan Lavallée; Kai-Uwe Hess; Jackie E. Kendrick; Jonathan M. Castro; Daniel Weidendorfer; Shane M. Rooyakkers; Annabelle Foster; Lucy E. Jackson; Ben M. Kennedy; Alexander R.L. Nichols; et al. (Journal of Volcanology and Geothermal Research, 2024)

Historic ocean acidification of Loch Sween revealed by correlative geochemical imaging and high-resolution boron isotope analysis of Boreolithothamniom cf. soriferum - Ellen MacDonald; Gavin L. Foster; Christopher D. Standish; Jacob Trend; Tessa M. Page; Nicholas A. Kamenos (Earth and Planetary Science Letters, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Constitutive and numerical modelling for timber-metal connections under large deformations - L. M. Milindu B. Jayasekara; Robert M. Foster (Engineering Structures, 2024)

Control of cyanobacterial growth with potassium; implications for bloom control in nuclear storage ponds - Kejing Zhang; Lynn Foster; Christopher Boothman; Naji M. Bassil; Jon K. Pittman; Jonathan R. Lloyd (Harmful Algae, 2024)

Mechanistic safety assessment via multi-omic characterisation of systemic pathway perturbations following in vivo MAT2A inhibition - Valentina Fogal; Filippos Michopoulos; Andrew F. Jarnuczak; Ghaith M. Hamza; Stephanie Harlfinger; Paul Davey; Heather Hulme; Stephen J. Atkinson; Piotr Gabrowski; Tony Cheung; Michael Grondine; Clare Hoover; et al. (Archives of Toxicology, 2024)
The tumour suppressor p16/CDKN2A and the metabolic gene, methyl-thio-adenosine phosphorylase (MTAP), are frequently co-deleted in some of the most aggressive and currently untreatable cancers. Cells with MTAP deletion are vulnerable to inhibition of the metabolic enzyme, methionine-adenosyl transferase 2A (MAT2A), and the protein arginine methyl transferase (PRMT5). This synthetic lethality has paved the way for the rapid development of drugs targeting the MAT2A/PRMT5 axis. MAT2A and its liver- and pancreas-specific isoform, MAT1A, generate the universal methyl donor S-adenosylmethionine (SAM) from ATP and methionine. Given the pleiotropic role SAM plays in methylation of diverse substrates, characterising the extent of SAM depletion and downstream perturbations following MAT2A/MAT1A inhibition (MATi) is critical for safety assessment. We have assessed in vivo target engagement and the resultant systemic phenotype using multi-omic tools to characterise response to a MAT2A inhibitor (AZ’9567). We observed significant SAM depletion and extensive methionine accumulation in the plasma, liver, brain and heart of treated rats, providing the first assessment of both global SAM depletion and evidence of hepatic MAT1A target engagement. An integrative analysis of multi-omic data from liver tissue identified broad perturbations in pathways covering one-carbon metabolism, trans-sulfuration and lipid metabolism. We infer that these pathway-wide perturbations represent adaptive responses to SAM depletion and confer a risk of oxidative stress, hepatic steatosis and an associated disturbance in plasma and cellular lipid homeostasis. The alterations also explain the dramatic increase in plasma and tissue methionine, which could be used as a safety and PD biomarker going forward to the clinic.

Deliberately introduced dung beetles in A ustralia: 12 years of occurrence and abundance records from 2001 to 2022 - Jacob D. Berson; Penelope B. Edwards; T. James Ridsdill‐Smith; Christopher K. Taylor; Daniel J. Anderson; Nigel R. Andrew; Russell A. Barrow; David A. Cousins; Robert N. Emery; Laura L. Fagan; Rhiannon M. Foster; Lucas G. Harwood; et al. (Ecology, 2024)
Since 1968, the Australian Dung Beetle Project has carried out field releases of 43 deliberately introduced dung beetle species for the biological control of livestock dung and dung‐breeding pests. Of these, 23 species are known to have become established. For most of these species, sufficient time has elapsed for population expansion to fill the extent of their potential geographic range through both natural and human‐assisted dispersal. Consequently, over the last 20 years, extensive efforts have been made to quantify the current distribution of these introduced dung beetles, as well as the seasonal and spatial variation in their activity levels. Much of these data and their associated metadata have remained unpublished, and they have not previously been synthesized into a cohesive dataset. Here, we collate and report data from the three largest dung beetle monitoring projects from 2001 to 2022. Together, these projects encompass data collected from across Australia, and include records for all 23 species of established dung beetles introduced for biocontrol purposes. In total, these data include 22,718 presence records and 213,538 absence records collected during 10,272 sampling events at 546 locations. Most presence records (97%) include abundance data. In total, 1,752,807 dung beetles were identified as part of these data. The distributional occurrence and abundance data can be used to explore questions such as factors influencing dung beetle species distributions, dung beetle biocontrol, and insect‐mediated ecosystem services. These data are provided under a CC‐BY‐NC 4.0 license and users are encouraged to cite this data paper when using the data.

Effects of alternative hermetic bag storage on fermented and dried cocoa bean (Theobroma cacao L.) - Kenneth A. Foster; Lina M. Suarez-Guzman; Diana C. Meza-Sepulveda; Dieudonne Baributsa; Carlos A. Zurita (Journal of Stored Products Research, 2024)

Synthesis and applications of manganese oxide - biochar composites: A systematic review across catalysis, capacitor and sorption applications - Flora M. Brocza; Stella J. Foster; Caroline L. Peacock; Jenny M. Jones (Biomass and Bioenergy, 2024)

Advances in life‐history knowledge for 35 seahorse species from community science - Elsa Camins; Lily M. Stanton; Miguel Correia; Sarah J. Foster; Heather J. Koldewey; Amanda C. J. Vincent (Journal of Fish Biology, 2024)
Marine community science presents an important route to gather valuable scientific information while also influencing local management and policy, thus contributing to marine conservation efforts. Because seahorses are cryptic but charismatic species, they are good candidates for engaging diverse people to help overcome the many gaps in biological knowledge. We have synthesized information contributed to the community science project iSeahorse from October 2013 to April 2022 for 35 of 46 known seahorse species. We then compared the obtained results with information in existing IUCN Red List assessments, executed from 2014 to 2017, to explore the potential of iSeahorse in expanding seahorse knowledge. Our results show updated geographic ranges for 7 seahorse species, new habitats described for 24 species, observations outside the previously recorded depth range for 14 species, and new information on sex ratio for 15 species and on pregnancy seasonality for 11 species. As one example of the power of iSeahorse, contributed observations on Coleman's pygmy seahorse ( Hippocampus colemani ) indicated that its geographic range is thousands of square kilometers larger, its habitat more diverse, and its depth range shallower than previously known. It is clear that iSeahorse is expanding knowledge on seahorses to a level that will help improve IUCN Red List assessments. The power of community science for marine conservation in general needs to be fully explored.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Journals must expand access to peer review data - Olivia M. Smith; Kayla L. Davis; Robin Waterman; Riley B. Pizza; Caitlin Mack; Emily E. Conway; Kara C. Dobson; Brianna Foster; Ani E. Hristova; Julie C. Jarvey; Nan Nourn; Courtney L. Davis (Trends in Ecology & Evolution, 2024)

Organophosphate ester flame retardants and plasticizers in house dust and mental health outcomes among Canadian mothers: A nested prospective cohort study in CHILD - Stephanie A. Foster; Molly L. Kile; Perry Hystad; Miriam L. Diamond; Liisa M. Jantunen; Piush J. Mandhane; Theo J. Moraes; Garthika Navaranjan; James A. Scott; Elinor Simons; Padmaja Subbarao; Tim K. Takaro; et al. (Environmental Research, 2024)

DNA metabarcoding reveals diet composition of invasive rats and mice in Hawaiian forests - Sara M. E. Gabrielson; Rebecca L. Mau; Erika Dittmar; J. Patrick Kelley; Corey E. Tarwater; Donald R. Drake; Jinelle H. Sperry; Jeffrey T. Foster (Biological Invasions, 2024)

Both ‘firmer’ and ‘queachy’: drainage of the lands along the Lincolnshire Wash in the seventeenth century - I. G. Simmons; M. R. Foster (Water History, 2023)

Measurement of 24 phthalate metabolites in 1st trimester urine samples: The MIREC study - Tye E. Arbuckle; Éric Gaudreau; Susan MacPherson; Muzeyyen Kabasakal; Michael M. Borghese; Mandy Fisher; Maryse F. Bouchard; Warren Foster; Jillian Ashley-Martin; Gilles Provencher (Chemosphere, 2023)

A Comparison of Infant Diet Quality Indices in Infants 7-12 Months Old - S. Foster; D. Jacobvitz; L. Hernandez; H. Jones; M. Abrego; E. Widen (Journal of the Academy of Nutrition and Dietetics, 2023)

Host infection and disease‐induced mortality modify species contributions to the environmental reservoir - Nichole A. Laggan; Katy L. Parise; J. Paul White; Heather M. Kaarakka; Jennifer A. Redell; John E. DePue; William H. Scullon; Joseph Kath; Jeffrey T. Foster; A. Marm Kilpatrick; Kate E. Langwig; Joseph R. Hoyt (Ecology, 2023)
Environmental pathogen reservoirs exist for many globally important diseases and can fuel epidemics, influence pathogen evolution, and increase the threat of host extinction. Species composition can be an important factor that shapes reservoir dynamics and ultimately determines the outcome of a disease outbreak. However, disease‐induced mortality can change species communities, indicating that species responsible for environmental reservoir maintenance may change over time. Here we examine the reservoir dynamics of Pseudogymnoascus destructans , the fungal pathogen that causes white‐nose syndrome in bats. We quantified changes in pathogen shedding, infection prevalence and intensity, host abundance, and the subsequent propagule pressure imposed by each species over time. We find that highly shedding species are important during pathogen invasion, but contribute less over time to environmental contamination as they also suffer the greatest declines. Less infected species remain more abundant, resulting in equivalent or higher propagule pressure. More broadly, we demonstrate that high infection intensity and subsequent mortality during disease progression can reduce the contributions of high‐shedding species to long‐term pathogen maintenance.

Trophic Niche Metrics Reveal Long-Term Shift in Florida Bay Food Webs - Stacy Calhoun-Grosch; Emelie M. Foster; W. Ryan James; Rolando O. Santos; Jennifer S. Rehage; James A. Nelson (Ecosystems, 2023)

ebony underpins Batesian mimicry in melanic stoneflies - Brodie J. Foster; Graham A. McCulloch; Yasmin Foster; Gracie C. Kroos; Tania M. King; Jonathan M. Waters (Molecular Ecology, 2023)
The evolution of Batesian mimicry – whereby harmless species avoid predation through their resemblance to harmful species – has long intrigued biologists. In rare cases, Batesian mimicry is linked to intraspecific colour variation, in which only some individuals within a population resemble a noxious ‘model’. Here, we assess intraspecific colour variation within a widespread New Zealand stonefly, wherein highly melanized individuals of Zelandoperla closely resemble a chemically defended aposematic stonefly, Austroperla cyrene . We assess convergence in the colour pattern of these two species, compare their relative palatability to predators, and use genome‐wide association mapping to assess the genetic basis of this resemblance. Our analysis reveals that melanized Zelandoperla overlap significantly with Austroperla in colour space but are significantly more palatable to predators, implying that they are indeed Batesian mimics. Analysis of 194,773 genome‐wide SNPs reveals an outlier locus ( ebony ) strongly differentiating melanic versus non‐melanic Zelandoperla . Genotyping of 338 specimens from a single Zelandoperla population indicates that ebony explains nearly 70% of the observed variance in melanism. As ebony has a well‐documented role in insect melanin biosynthesis, our findings indicate this locus has a conserved function across deeply divergent hexapod lineages. Distributional records suggest a link between the occurrence of melanic Zelandoperla and the forested ecosystems where the model Austroperla is abundant, suggesting the potential for adaptive shifts in this system underpinned by environmental change.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

The distribution of metal and petroleum-derived contaminants within sediments around oil and gas infrastructure in the Gippsland Basin, Australia - Sharon E. Hook; Scott Foster; Franziska Althaus; Douglas Bearham; Brad M. Angel; Andrew T. Revill; Stuart L. Simpson; Joanna Strzelecki; Tom Cresswell; Keith R. Hayes (Marine Pollution Bulletin, 2023)

A scenario-specific nexus modelling toolkit to identify trade-offs in the promotion of sustainable irrigated agriculture in Ecuador, a Belt and Road country - L. Naranjo; M.E. Correa-Cano; D. Rey; R. Chengot; F. España; M. Sactic; J.W. Knox; X. Yan; O. Viteri-Salazar; W. Foster; O. Melo (Journal of Cleaner Production, 2023)

Correction: Impact of nitrogen (N) and phosphorus (P) enrichment and skewed N:P stoichiometry on the skeletal formation and microstructure of symbiotic reef corals - M. C. Buckingham; C. D’Angelo; T. B. Chalk; G. L. Foster; K. G. Johnson; Z. Connelly; C. Olla; M. Saeed; J. Wiedenmann (Coral Reefs, 2023)

Geochemical responses of scleractinian corals to nutrient stress - C.D. Standish; T.B. Chalk; M. Saeed; F. Lei; M.C. Buckingham; C. D'Angelo; J. Wiedenmann; G.L. Foster (Geochimica et Cosmochimica Acta, 2023)

Negative outcomes of novel trophic interactions along mangrove range edges - Janelle A. Goeke; Emelie M. Foster; Anna R. Armitage (Ecology, 2023)
Tropicalization is a phenomenon that is changing the structure of ecosystems around the world. Mangrove encroachment is a particular form of tropicalization that may have cascading consequences for resident fauna in subtropical coastal wetlands. There is a knowledge gap regarding the extent of interactions between basal consumers and mangroves along mangrove range edges and the consequences of these novel interactions for consumers. This study focuses on the key coastal wetland consumers, Littoraria irrorata (marsh periwinkle) and Uca rapax (mudflat fiddler crabs), and their interactions with encroaching Avicennia germinans (black mangrove) in the Gulf of Mexico, USA. In food preference assays, Littoraria avoided consuming Avicennia and selectively ingested leaf tissue from a common marsh grass, Spartina alterniflora (smooth cordgrass), a preference that was also previously documented in Uca . The quality of Avicennia as a food source was determined by measuring the energy storage of consumers that had interacted with either Avicennia or marsh plants in the lab and the field. Littoraria and Uca both stored ~10% less energy when interacting with Avicennia , despite their different feeding behaviors and physiologies. The negative consequences of mangrove encroachment for these species at the individual level suggest that there may be negative population‐level effects as encroachment continues. Many studies have documented shifts in floral and faunal communities following mangrove replacement of salt marsh vegetation, but this study is the first to identify physiological responses that may be contributing to these shifts.

46 Pedigree tracing to determine origins of the Palomino Horse Breeders of America stock-type horse - E. North; M. Foster; J. Culwell; M. Nicodemus; T. Williams (Journal of Equine Veterinary Science, 2023)

The exposed Mule Creek vent deposits record the structure of a volcanic conduit during a hybrid explosive–effusive eruption - Holly E. Unwin; Hugh Tuffen; Fabian B. Wadsworth; Emrys R. Phillips; Mike R. James; Annabelle Foster; Stephan Kolzenburg; Jonathan M. Castro; Lucy A. Porritt (Bulletin of Volcanology, 2023)
Silicic volcanic eruptions commonly begin with the explosive ejection of pyroclastic material, before transitioning to gentler effusion-dominated activity. Well-exposed dissected silicic systems are scarce and poorly studied, hindering the advances in our understanding of the explosive–effusive transition needed to improve interpretations of volcanic unrest and hazard forecasting. The Mule Creek vent (New Mexico, USA) is a dissected silicic conduit that records the processes controlling conduit formation and evolution, and the role tuffisites (fractures filled with variably welded pyroclasts) play in conduit dynamics. Here, we use decimeter-scale photo-mapping of lithostratigraphic units and thin section analysis to differentiate and interpret three dominant emplacement styles during vent evolution. First, there was repeated deposition and erosion of pyroclastic material at the conduit walls, recorded by erosive surfaces in pyroclastic breccia and agglomerates at the conduit margins. Second, sub-vertical domains of dense melt-dominated magma were emplaced and preserved as glass-dominated vitrophyre and brecciated vitrophyre, with the textural hallmarks of assembly from welding of pyroclasts. Finally, the sub-horizontal fracturing of previously deposited lithologies produced laterally cross-cutting tuffisites. The vent deposits track the widening and then narrowing of the conduit through time and reflect progressive insulation and generally higher temperatures towards the conduit center as pyroclasts accumulate. Welding of pyroclastic fill and the formation of dense vitrophyres towards the conduit center lowers deposit porosity and effective wall permeability. This drives localized gas pressure increases and results in gas-driven fracturing, generating tuffisites, which act as transient outgassing pathways. The structure of the Mule Creek vent records an explosive–effusive transition, constraining the processes controlling conduit evolution and aiding our interpretation of volcanic unrest.

Asymmetry in the spin-up of a stratified fluid in a sliced, square cylinder - R. J. Munro; M. R. Foster (Environmental Fluid Mechanics, 2023)
Previously, we have reported theory and experiments on the spin-up of a linearly stratified fluid contained in a sealed square cylinder with a bottom sloped at angle $$α$$ α (Munro & Foster, Phys. Fluids , 26 , 026603, 2014). The motion is characterized by the small Rossby number, $$ε$$ ϵ , the fractional change in the rotation rate, the Ekman number, E , and the Burger number, S , the square of the ratio of the buoyancy frequency (or Brunt-Väisälä frequency) to the base rotation rate. This paper, supplementing what has gone before, is focused on the horizontal and vertical structure of the propagating vorticity waves (Rossby waves), with alternating anti-cyclonic and cyclonic cells, which move across the tank from east to west, thereby accomplishing at least the early stages of the spin-up. We find strong dependence of the modal structure of these Rossby waves, and their speed, on the Burger number. However, what is particularly noteworthy is the observed strong north-south asymmetry of the wave field. We find that the asymmetry is not consistent with typical Rossby-wave theories (Pedlosky and Greenspan, J. Fluid Mech. , 27 , p. 291, 1967), but is attributable to second-order effects in the asymptotic expansion of the streamfuntion in powers of $$α$$ α .

Caribbean–South America interactions since the Late Cretaceous: Insights from zircon U–Pb and Lu–Hf isotopic data in sedimentary sequences of the northwestern Andes - M. Botero-Garcia; C.J. Vinasco; S.A. Restrepo-Moreno; D.A. Foster; G.D. Kamenov (Journal of South American Earth Sciences, 2023)

Surface displacement expression of progressive failure in a sensitive clay landslide observed with long-term UAV monitoring - Michael J. Bentley; Jonathan M. Foster; Joshua J. Potvin; George Bevan; James Sharp; David J. Woeller; W. Andy Take (Landslides, 2023)

Variant-specific SARS-CoV-2 shedding rates in wastewater - Sarah M. Prasek; Ian L. Pepper; Gabriel K. Innes; Stephanie Slinski; Walter Q. Betancourt; Aidan R. Foster; Hayley D. Yaglom; W. Tanner Porter; David M. Engelthaler; Bradley W. Schmitz (Science of The Total Environment, 2023)

Urinary concentrations and determinants of glyphosate and glufosinate in pregnant Canadian participants in the MIREC study - Jillian Ashley-Martin; Rong Huang; Susan MacPherson; Orly Brion; James Owen; Eric Gaudreau; Jean-Francois Bienvenu; Mandy Fisher; Michael M. Borghese; Maryse F. Bouchard; Bruce Lanphear; Warren G. Foster; et al. (Environmental Research, 2023)

Boron isotopes in blue diamond record seawater-derived fluids in the lower mantle - Margo E. Regier; Karen V. Smit; Thomas B. Chalk; Thomas Stachel; Richard A. Stern; Evan M. Smith; Gavin L. Foster; Yannick Bussweiler; Chris DeBuhr; Antony D. Burnham; Jeff W. Harris; D. Graham Pearson (Earth and Planetary Science Letters, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Impact of nitrogen (N) and phosphorus (P) enrichment and skewed N:P stoichiometry on the skeletal formation and microstructure of symbiotic reef corals - M. C. Buckingham; C. D’Angelo; T. B. Chalk; G. L. Foster; K. G. Johnson; Z. Connelly; C. Olla; M. Saeed; J. Wiedenmann (Coral Reefs, 2022)
Reported divergent responses of coral growth and skeletal microstructure to the nutrient environment complicate knowledge-based management of water quality in coral reefs. By re-evaluating published results considering the taxonomy of the studied corals and the N:P stoichiometry of their nutrient environment, we could resolve some of the major apparent contradictions. Our analysis suggests that Acroporids behave differently to several other common genera and show distinct responses to specific nutrient treatments. We hypothesised that both the concentrations of dissolved inorganic N and P in the water and their stoichiometry shape skeletal growth and microstructure. We tested this hypothesis by exposing Acropora polystoma fragments to four nutrient treatments for > 10 weeks: high nitrate/high phosphate (HNHP), high nitrate/low phosphate (HNLP), low nitrate/high phosphate (LNHP) and low nitrate/low phosphate (LNLP). HNHP corals retained high zooxanthellae densities and their linear extension and calcification rates were up to ten times higher than in the other treatments. HNLP and LNLP corals bleached through loss of symbionts. The photochemical efficiency (Fv/Fm) of residual symbionts in HNLP corals was significantly reduced, indicating P-starvation. Micro-computed tomography (µCT) of the skeletal microstructure revealed that reduced linear extension in nutrient limited or nutrient starved conditions (HNLP, LNHP, LNLP) was associated with significant thickening of skeletal elements and reduced porosity. These changes can be explained by the strongly reduced linear extension rate in combination with a smaller reduction in the calcification rate. Studies using increased skeletal density as a proxy for past thermal bleaching events should consider that such an increase in density may also be associated with temperature-independent response to the nutrient environment. Furthermore, the taxonomy of corals and seawater N:P stoichiometry should be considered when analysing and managing the impacts of nutrient pollution.

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Nitrogen Fertilizer, Arbuscular Mycorrhizal Fungi, and Soil Nematodes Affect Lignin Quality and Quantity in Switchgrass (Panicum virgatum L.) - Binod Basyal; Cliff Foster; Katherine L. Gross; Sarah M. Emery (BioEnergy Research, 2022)

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Genomic characterization of silvergrass cryptic virus 1, a novel partitivirus infecting Miscanthus sinensis - Larissa C. Costa; Xiaojun Hu; Martha Malapi-Wight; Mary O’Connell; Leticia M. Hendrickson; Roy S. Turner; Clint McFarland; Joseph Foster; Oscar P. Hurtado-Gonzales (Archives of Virology, 2022)

Determinants of community compositional change are equally affected by global change - Meghan L. Avolio; Kimberly J. Komatsu; Scott L. Collins; Emily Grman; Sally E. Koerner; Andrew T. Tredennick; Kevin R. Wilcox; Sara Baer; Elizabeth H. Boughton; Andrea J. Britton; Bryan Foster; Laura Gough; et al. (Ecology Letters, 2021)
Global change is impacting plant community composition, but the mechanisms underlying these changes are unclear. Using a dataset of 58 global change experiments, we tested the five fundamental mechanisms of community change: changes in evenness and richness, reordering, species gains and losses. We found 71% of communities were impacted by global change treatments, and 88% of communities that were exposed to two or more global change drivers were impacted. Further, all mechanisms of change were equally likely to be affected by global change treatments—species losses and changes in richness were just as common as species gains and reordering. We also found no evidence of a progression of community changes, for example, reordering and changes in evenness did not precede species gains and losses. We demonstrate that all processes underlying plant community composition changes are equally affected by treatments and often occur simultaneously, necessitating a wholistic approach to quantifying community changes.

Cerebellar Grey Matter Volume in Older Persons Is Associated with Worse Cognitive Functioning - A. Buhrmann; A. M. A. Brands; J. van der Grond; C. Schilder; R. C. van der Mast; N. Rius Ottenheim; J. C. Foster-Dingley; A. S. Bertens; E. van den Berg (The Cerebellum, 2021)

The multiple process model of goal-directed aiming/reaching: insights on limb control from various special populations - Digby Elliott; James Lyons; Spencer J. Hayes; James J. Burkitt; Steve Hansen; Lawrence E. M. Grierson; Nathan C. Foster; James W. Roberts; Simon J. Bennett (Experimental Brain Research, 2020)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Quantifying the impacts of abrasion and bacterial transfer when fish are exposed to sand during a catch-and-release event - RM Foster; A-R Childs; M Brooks; MW Farthing; EC Butler; WM Potts (African Journal of Marine Science, 2020)

Differential Effect of Repeated Lipopolysaccharide Treatment and Aging on Hippocampal Function and Biomarkers of Hippocampal Senescence - Jolie Barter; Ashok Kumar; Asha Rani; Luis M Colon-Perez; Marcelo Febo; Thomas C. Foster (Molecular Neurobiology, 2020)

Direct administration of ifenprodil and citalopram into the nucleus accumbens inhibits cue-induced nicotine seeking and associated glutamatergic plasticity - Jonna M. Leyrer-Jackson; Jose A. Piña; Joseph McCallum; M. Foster Olive; Cassandra D. Gipson (Brain Structure and Function, 2020)

Information Needs for Treatment Decision-making of Hematopoietic Cell Transplant Patients 65 Years or Older and Caregivers - Jackie Foster; Heather Moore; Jaime M. Preussler; Linda J. Burns; Jenna Hullerman Umar; Brett Glotzbecker; Shirley Johnson; Hannah MacDougall; Lih-Wen Mau; Elizabeth A. Murphy; Celalettin Ustun; Stacy Stickney Ferguson; et al. (Journal of Cancer Education, 2020)

Comparing the fate of brain metastatic breast cancer cells in different immune compromised mice with cellular magnetic resonance imaging - Natasha N. Knier; Amanda M. Hamilton; Paula J. Foster (Clinical & Experimental Metastasis, 2020)

Emergence of an evolutionary innovation: Gene expression differences associated with the transition between oviparity and viviparity - Charles S. P. Foster; Michael B. Thompson; James U. Van Dyke; Matthew C. Brandley; Camilla M. Whittington (Molecular Ecology, 2020)
Our understanding of the evolution of complex biological traits is greatly advanced by examining taxa with intermediate phenotypes. The transition from oviparity (egg‐laying) to viviparity (live‐bearing) has occurred independently in many animal lineages, but there are few phenotypic intermediates. The lizard Saiphos equalis exhibits bimodal reproduction, with some viviparous populations, and other oviparous populations with long egg‐retention, a rare trait where most of embryonic development occurs inside the mother prior to late ovipositioning. We posit that oviparous S. equalis represent an intermediate form between “true” oviparity and viviparity. We used transcriptomics to compare uterine gene expression in these two phenotypes, and provide a molecular model for the genetic control and evolution of reproductive mode. Many genes are differentially expressed throughout the reproductive cycle of both phenotypes, which have clearly different gene expression profiles overall. The differentially expressed genes within oviparous and viviparous individuals have broadly similar biological functions putatively important for sustaining embryos, including uterine remodelling, respiratory gas and water exchange, and immune regulation. These functional similarities indicate either that long egg‐retention is an exaptation for viviparity, or might reflect parallel evolution of similar gravidity‐related changes in gene expression in long egg‐retention oviparity. In contrast, gene expression changes across the reproductive cycle of long egg‐retaining oviparous S. equalis are dramatically different from those of “true” oviparous skinks (such as Lampropholis guichenoti ), supporting our assertion that oviparous S. equalis exhibit an intermediate phenotype between “true” oviparity and viviparity.

Paternally‐biased gene expression follows kin‐selected predictions in female honey bee embryos - Nicholas M. A. Smith; Boris Yagound; Emily J. Remnant; Charles S. P. Foster; Gabriele Buchmann; Michael H. Allsopp; Clement F. Kent; Amro Zayed; Stephen A. Rose; Kitty Lo; Alyson Ashe; Brock A. Harpur; et al. (Molecular Ecology, 2020)
The Kinship Theory of Genomic Imprinting (KTGI) posits that, in species where females mate with multiple males, there is selection for a male to enhance the reproductive success of his offspring at the expense of other males and his mating partner. Reciprocal crosses between honey bee subspecies show parent‐of‐origin effects for reproductive traits, suggesting that males modify the expression of genes related to female function in their female offspring. This effect is likely to be greater in the Cape honey bee ( Apis mellifera capensis ), because a male's daughters have the unique ability to produce female offspring that can develop into reproductive workers or the next queen without mating. We generated reciprocal crosses between Capensis and another subspecies and used RNA‐seq to identify transcripts that are over‐ or underexpressed in the embryos, depending on the parental origin of the gene. As predicted, 21 genes showed expression bias towards the Capensis father's allele in colonies with a Capensis father, with no such bias in the reciprocal cross. A further six genes showed a consistent bias towards expression of the father's allele across all eight colonies examined, regardless of the direction of the cross. Consistent with predictions of the KTGI, six of the 21 genes are associated with female reproduction. No gene consistently showed overexpression of the maternal allele .

Mating type determination within a microsatellite multiplex for the fungal pathogen Pseudogymnoascus destructans, the causative agent of white-nose disease in bats - Serena Dool; Andrea Altewischer; Nicola M. Fischer; Kevin P. Drees; Jeffrey T. Foster; Marcus Fritze; Sebastien J. Puechmaille (Conservation Genetics Resources, 2020)

Biogeography of epibenthic assemblages in the central Beaufort Sea - Alexandra M Ravelo; Bodil A. Bluhm; Nora Foster; Katrin Iken (Marine Biodiversity, 2020)

Utilization of infectious clones to visualize Cassava brown streak virus replication in planta and gain insights into symptom development - Katie R. Tomlinson; Susan E. Seal; Andy M. Bailey; Gary D. Foster (Virus Genes, 2019)

Designing Monitoring Programs for Marine Protected Areas Within an Evidence Based Decision Making Paradigm - Keith R. Hayes; Geoffrey R. Hosack; Emma Lawrence; Paul Hedge; Neville S. Barrett; Rachel Przeslawski; M. Julian Caley; Scott D. Foster (Frontiers in Marine Science, 2019)

Remotely Sensed Winds and Wind Stresses for Marine Forecasting and Ocean Modeling - Mark A. Bourassa; Thomas Meissner; Ivana Cerovecki; Paul S. Chang; Xiaolong Dong; Giovanna De Chiara; Craig Donlon; Dmitry S. Dukhovskoy; Jocelyn Elya; Alexander Fore; Melanie R. Fewings; Ralph C. Foster; et al. (Frontiers in Marine Science, 2019)

The state of Western Australia’s coral reefs - James P. Gilmour; Kylie L. Cook; Nicole M. Ryan; Marjetta L. Puotinen; Rebecca H. Green; George Shedrawi; Jean-Paul A. Hobbs; Damian P. Thomson; Russell C. Babcock; Joanna Buckee; Taryn Foster; Zoe T. Richards; et al. (Coral Reefs, 2019)

Ecology of a versatile canid in the Neotropics: gray foxes (Urocyon cinereoargenteus) in Belize, Central America - Bart J. Harmsen; Emma Sanchez; Omar A. Figueroa; Said M. Gutierrez; C. Patrick Doncaster; Rebecca J. Foster (Mammal Research, 2019)

Ecological gradients drive insect wing loss and speciation: The role of the alpine treeline - Graham A. McCulloch; Brodie J. Foster; Ludovic Dutoit; Travis Ingram; Eleanor Hay; Andrew J. Veale; Peter K. Dearden; Jonathan M. Waters (Molecular Ecology, 2019)
Alpine ecosystems are frequently characterized by an abundance of wing‐reduced insect species, but the drivers of this biodiversity remain poorly understood. Insect wing reduction in these environments has variously been attributed to altitude, temperature, isolation, habitat stability or decreased habitat size. We used fine‐scale ecotypic and genomic analyses, along with broad‐scale distributional analyses of ecotypes, to unravel the ecological drivers of wing reduction in the wing‐dimorphic stonefly Zelandoperla fenestrata complex. Altitudinal transects within populations revealed dramatic wing reduction over very fine spatial scales, tightly linked to the alpine treeline. Broad biogeographical analyses confirm that the treeline has a much stronger effect on these ecotype distributions than altitude per se. Molecular analyses revealed parallel genomic divergence between vestigial‐winged (high altitude) and full‐winged (low altitude) ecotypes across distinct streams. These data thus highlight the role of the alpine treeline as a key driver of rapid speciation, providing a new model for ecological diversification along exposure gradients.

Trends and indicators for quantifying moth abundance and occupancy in Scotland - E. B. Dennis; T. M. Brereton; B. J. T. Morgan; R. Fox; C. R. Shortall; T. Prescott; S. Foster (Journal of Insect Conservation, 2019)

Cognitive deficits and neurotoxicity induced by synthetic cathinones: is there a role for neuroinflammation? - Jonna M. Leyrer-Jackson; Erin K. Nagy; M. Foster Olive (Psychopharmacology, 2019)

The effects of trehalose glycolipid presentation on cytokine production by GM-CSF macrophages - Bridget L. Stocker; Kristel Kodar; Kanu Wahi; Amy J. Foster; Jacquie L. Harper; Daiki Mori; Sho Yamasaki; Mattie S. M. Timmer (Glycoconjugate Journal, 2019)

Impact of irrigated agriculture on groundwater-recharge salinity: a major sustainability concern in semi-arid regions - Stephen Foster; Antonio Pulido-Bosch; Ángela Vallejos; Luis Molina; Armando Llop; Alan M. MacDonald (Hydrogeology Journal, 2018)

Analysis of novel domain-specific mutations in the zebrafish ndr2/cyclops gene generated using CRISPR-Cas9 RNPs - Ashley N. Turner; Reagan S. Andersen; Ivy E. Bookout; Lauren N. Brashear; James C. Davis; David M. Gahan; John P. Gotham; Baraa A. Hijaz; Ashish S. Kaushik; Jordan B. Mcgill; Victoria L. Miller; Zachariah P. Moseley; et al. (Journal of Genetics, 2018)

Reproducible multi-parameter acoustic detection of seasonal drift macroalgae in the Indian River Lagoon, Florida - G. Foster; B. M. Riegl; L. J. Morris; K. A. Foster (Journal of Coastal Conservation, 2018)

Correction to: Polarisation vision: overcoming challenges of working with a property of light we barely see - James J. Foster; Shelby E. Temple; Martin J. How; Ilse M. Daly; Camilla R. Sharkey; David Wilby; Nicholas W. Roberts (The Science of Nature, 2018)

Polarisation vision: overcoming challenges of working with a property of light we barely see - James J. Foster; Shelby E. Temple; Martin J. How; Ilse M. Daly; Camilla R. Sharkey; David Wilby; Nicholas W. Roberts (The Science of Nature, 2018)

Spatial and temporal interactions of free-ranging pacas (Cuniculus paca) - Bart J. Harmsen; Rebecca L. Wooldridge; Said M. Gutierrez; C. Patrick Doncaster; Rebecca J. Foster (Mammal Research, 2018)

Investigating the Complex Association Between Viral Ecology, Environment, and Northeast Pacific Sea Star Wasting - Ian Hewson; Kalia S. I. Bistolas; Eva M. Quijano Cardé; Jason B. Button; Parker J. Foster; Jacob M. Flanzenbaum; Jan Kocian; Chaunte K. Lewis (Frontiers in Marine Science, 2018)

Association of citrus leafminer Phyllocnistis citrella (Lepidoptera: Gracillariidae) damage with physiological parameters and larval weight in Citrus reticulata - Muhammad Arshad; Muhammad Irfan Ullah; Muhammad Afzal; Hafiz M. Aatif; Yasir Iftikhar; Jaime Molina-Ochoa; John E. Foster (International Journal of Tropical Insect Science, 2018)

Loss of the nutrient sensor TAS1R3 leads to reduced bone resorption - Michael S. Eaton; Nicholas Weinstein; Jordan B. Newby; Maggie M. Plattes; Hanna E. Foster; Jon W. Arthur; Taylor D. Ward; Stephen R. Shively; Ryann Shor; Justin Nathan; Hannah M. Davis; Lilian I. Plotkin; et al. (Journal of Physiology and Biochemistry, 2018)

A year in the life of a thrombolite: comparative metatranscriptomics reveals dynamic metabolic changes over diel and seasonal cycles - Artemis S. Louyakis; Hadrien Gourlé; Giorgio Casaburi; Rachelle M. E. Bonjawo; Alexandrea A. Duscher; Jamie S. Foster (Environmental Microbiology, 2018)
Summary Microbialites are one of the oldest known ecosystems on Earth and the coordinated metabolisms and activities of these mineral‐depositing communities have had a profound impact on the habitability of the planet. Despite efforts to understand the diversity and metabolic potential of these systems, there has not been a systematic molecular analysis of the transcriptional changes that occur within a living microbialite over time. In this study, we generated metatranscriptomic libraries from actively growing thrombolites, a type of microbialite, throughout diel and seasonal cycles and observed dynamic shifts in the population and metabolic transcriptional activity. The most transcribed genes in all seasons were associated with photosynthesis, but only transcripts associated with photosystem II exhibited diel cycling. Photosystem I transcripts were constitutively expressed at all time points including midnight and sunrise. Transcripts associated with nitrogen fixation, methanogenesis and dissimilatory sulfate reduction exhibited diel cycling, and variability between seasons. Networking analysis of the metatranscriptomes showed correlated expression patterns helping to elucidate how metabolic interactions are coordinated within the thrombolite community. These findings have identified distinctive temporal patterns within the thrombolites and will serve an important foundation to understand the mechanisms by which these communities form and respond to changes in their environment.

Energy conserving thermoregulatory patterns and lower disease severity in a bat resistant to the impacts of white-nose syndrome - Marianne S. Moore; Kenneth A. Field; Melissa J. Behr; Gregory G. Turner; Morgan E. Furze; Daniel W. F. Stern; Paul R. Allegra; Sarah A. Bouboulis; Chelsey D. Musante; Megan E. Vodzak; Matthew E. Biron; Melissa B. Meierhofer; et al. (Journal of Comparative Physiology B, 2018)

Hydrogeological typologies of the Indo-Gangetic basin alluvial aquifer, South Asia - H. C. Bonsor; A. M. MacDonald; K. M. Ahmed; W. G. Burgess; M. Basharat; R. C. Calow; A. Dixit; S. S. D. Foster; K. Gopal; D. J. Lapworth; M. Moench; A. Mukherjee; et al. (Hydrogeology Journal, 2017)

Utility of spherical human liver microtissues for prediction of clinical drug-induced liver injury - William R. Proctor; Alison J. Foster; Jennifer Vogt; Claire Summers; Brian Middleton; Mark A. Pilling; Daniel Shienson; Monika Kijanska; Simon Ströbel; Jens M. Kelm; Paul Morgan; Simon Messner; et al. (Archives of Toxicology, 2017)

Similar dietary but different numerical responses to nonnative tamarisk (Tamarix spp.) by two native warblers - Sean M. Mahoney; Tad C. Theimer; Matthew J. Johnson; Jeffrey T. Foster (Biological Invasions, 2017)

MicroRNAs as therapeutics for future drug delivery systems in treatment of lung diseases - Kamal Dua; Nicole G. Hansbro; Paul S. Foster; Philip M. Hansbro (Drug Delivery and Translational Research, 2017)

In vivo magnetic resonance imaging investigating the development of experimental brain metastases due to triple negative breast cancer - Amanda M. Hamilton; Paula J. Foster (Clinical & Experimental Metastasis, 2017)

Lessons on Climate Sensitivity From Past Climate Changes - Anna S. von der Heydt; Henk A. Dijkstra; Roderik S. W. van de Wal; Rodrigo Caballero; Michel Crucifix; Gavin L. Foster; Matthew Huber; Peter Köhler; Eelco Rohling; Paul J. Valdes; Peter Ashwin; Sebastian Bathiany; et al. (Current Climate Change Reports, 2016)

Functional analysis of Agaricus bisporus serine proteinase 1 reveals roles in utilization of humic rich substrates and adaptation to the leaf‐litter ecological niche - Mary N. Heneghan; Claire Burns; Ana M. S. B. Costa; Kerry S. Burton; Michael P. Challen; Andy M. Bailey; Gary D. Foster (Environmental Microbiology, 2016)
Summary Agaricus bisporus is a secondary decomposer fungus and an excellent model for the adaptation, persistence and growth of fungi in humic‐rich environments such as soils of temperate woodland and pastures. The A. bisporus serine proteinase SPR1 is induced by humic acids and is highly expressed during growth on compost. Three Spr1 gene silencing cassettes were constructed around sense, antisense and non‐translatable‐stop strategies (pGRsensehph, pGRantihph and pGRstophph). Transformation of A. bisporus with these cassettes generated cultures showing a reduction in extracellular proteinase activity as demonstrated by the reduction, or abolition, of a clearing zone on plate‐based bioassays. These lines were then assessed by detailed enzyme assay, RT‐qPCR and fruiting. Serine proteinase activity in liquid cultures was reduced in 83% of transformants. RT‐qPCR showed reduced Spr1 mRNA levels in all transformants analysed, and these correlated with reduced enzyme activity. When fruiting was induced, highly‐silenced transformant AS5 failed to colonize the compost, whilst for those that did colonize the compost, 60% gave a reduction in mushroom yield. Transcriptional, biochemical and developmental observations, demonstrate that SPR1 has an important role in nutrient acquisition in compost and that SPR1 is a key enzyme in the adaptation of Agaricus to the humic‐rich ecological niche formed during biomass degradation.

Microbial dinitrogen fixation in coral holobionts exposed to thermal stress and bleaching - Ulisse Cardini; Nanne van Hoytema; Vanessa N. Bednarz; Laura Rix; Rachel A. Foster; Mamoon M. D. Al‐Rshaidat; Christian Wild (Environmental Microbiology, 2016)
Summary Coral holobionts (i.e., coral‐algal‐prokaryote symbioses) exhibit dissimilar thermal sensitivities that may determine which coral species will adapt to global warming. Nonetheless, studies simultaneously investigating the effects of warming on all holobiont members are lacking. Here we show that exposure to increased temperature affects key physiological traits of all members (herein: animal host, zooxanthellae and diazotrophs) of both Stylophora pistillata and Acropora hemprichii during and after thermal stress. S. pistillata experienced severe loss of zooxanthellae (i.e., bleaching) with no net photosynthesis at the end of the experiment. Conversely, A. hemprichii was more resilient to thermal stress. Exposure to increased temperature (+ 6°C) resulted in a drastic increase in daylight dinitrogen (N 2 ) fixation, particularly in A. hemprichii (threefold compared with controls). After the temperature was reduced again to in situ levels, diazotrophs exhibited a reversed diel pattern of activity, with increased N 2 fixation rates recorded only in the dark, particularly in bleached S. pistillata (twofold compared to controls). Concurrently, both animal hosts, but particularly bleached S. pistillata , reduced both organic matter release and heterotrophic feeding on picoplankton. Our findings indicate that physiological plasticity by coral‐associated diazotrophs may play an important role in determining the response of coral holobionts to ocean warming.

Spectrum of DNA variants for non-syndromic deafness in a large cohort from multiple continents - Denise Yan; Demet Tekin; Guney Bademci; Joseph Foster; F. Basak Cengiz; Abhiraami Kannan-Sundhari; Shengru Guo; Rahul Mittal; Bing Zou; Mhamed Grati; Rosemary I. Kabahuma; Mohan Kameswaran; et al. (Human Genetics, 2016)

Ecology and multilevel selection explain aggression in spider colonies - Jay M. Biernaskie; Kevin R. Foster (Ecology Letters, 2016)
Progress in sociobiology continues to be hindered by abstract debates over methodology and the relative importance of within‐group vs. between‐group selection. We need concrete biological examples to ground discussions in empirical data. Recent work argued that the levels of aggression in social spider colonies are explained by group‐level adaptation. Here, we examine this conclusion using models that incorporate ecological detail while remaining consistent with kin‐ and multilevel selection frameworks. We show that although levels of aggression are driven, in part, by between‐group selection, incorporating universal within‐group competition provides a striking fit to the data that is inconsistent with pure group‐level adaptation. Instead, our analyses suggest that aggression is favoured primarily as a selfish strategy to compete for resources, despite causing lower group foraging efficiency or higher risk of group extinction. We argue that sociobiology will benefit from a pluralistic approach and stronger links between ecologically informed models and data.

Effect of Gastric Fluid Volume on the In Vitro Dissolution and In Vivo Absorption of BCS Class II Drugs: a Case Study with Nifedipine - Ahmed M. Nader; Sara K. Quinney; Hala M. Fadda; David R. Foster (The AAPS Journal, 2016)

Inorganic Arsenic Concentrations in Wheat Chaff Exceed Those in Wheat Grain - Elliott G. Duncan; William A. Maher; Rajani Jagtap; Simon D. Foster; Frank Krikowa; Cathryn A. O’Sullivan; Margaret M. Roper (Water, Air, & Soil Pollution, 2016)

Characterization of innate immunity genes in the parasitic nematode Brugia malayi - Silvia Libro; Barton E. Slatko; Jeremy M. Foster (Symbiosis, 2016)

Global impacts of the 1980s regime shift - Philip C. Reid; Renata E. Hari; Grégory Beaugrand; David M. Livingstone; Christoph Marty; Dietmar Straile; Jonathan Barichivich; Eric Goberville; Rita Adrian; Yasuyuki Aono; Ross Brown; James Foster; et al. (Global Change Biology, 2016)
Despite evidence from a number of Earth systems that abrupt temporal changes known as regime shifts are important, their nature, scale and mechanisms remain poorly documented and understood. Applying principal component analysis, change‐point analysis and a sequential t ‐test analysis of regime shifts to 72 time series, we confirm that the 1980s regime shift represented a major change in the Earth's biophysical systems from the upper atmosphere to the depths of the ocean and from the Arctic to the Antarctic, and occurred at slightly different times around the world. Using historical climate model simulations from the Coupled Model Intercomparison Project Phase 5 ( CMIP 5) and statistical modelling of historical temperatures, we then demonstrate that this event was triggered by rapid global warming from anthropogenic plus natural forcing, the latter associated with the recovery from the El Chichón volcanic eruption. The shift in temperature that occurred at this time is hypothesized as the main forcing for a cascade of abrupt environmental changes. Within the context of the last century or more, the 1980s event was unique in terms of its global scope and scale; our observed consequences imply that if unavoidable natural events such as major volcanic eruptions interact with anthropogenic warming unforeseen multiplier effects may occur.

Effect of ocean warming and acidification on the early life stages of subtropical Acropora spicifera - T. Foster; J. P. Gilmour; C. M. Chua; J. L. Falter; M. T. McCulloch (Coral Reefs, 2015)

Short-horned grasshopper subfamilies feed at different rates on big bluestem and switchgrass cultivars - Muhammad Irfan Ullah; Fatima Mustafa; William W. Hoback; Mathew L. Brust; Kerri M. Farnsworth-Hoback; John E. Foster (Biologia, 2015)

Pollen–climate reconstruction from northern South Island, New Zealand (41°S), reveals varying high‐ and low‐latitude teleconnections over the last 16 000 years - Ignacio A. Jara; Rewi M. Newnham; Marcus J. Vandergoes; Courtney R. Foster; David J. Lowe; Janet M. Wilmshurst; Patricio I. Moreno; James A. Renwick; Aline M. Homes (Journal of Quaternary Science, 2015)
We present a 16 000‐year vegetation and climate reconstruction from pollen and plant macrofossil records obtained at a small alpine lake in South Island, New Zealand (41°S). The expansion of lowland forest taxa suggests a lifting of the altitudinal forest limits because of a warming pulse between 13 and 10k cal a BP and between 7 and 6k cal a BP, while their decline relative to upland forest taxa indicates cooling phases between 10 and 7k cal a BP and over the last 3000 years. The modern treeline was first established locally by 9.7k cal a BP. Forest persisted at the site until 3k cal a BP then disappeared from the record. Close correspondence between the temperature trends inferred from the pollen and macrofossil records and proxies from Antarctica and the Southern Ocean suggests a strong teleconnection between New Zealand and the Southern Hemisphere high‐latitudes between 15 and 6k cal a BP. We note that the breakdown of this coupling, a cooling trend in Adelaide Tarn and the local disappearance of beech forest after 3k cal a BP occur during a period of increased frequency of El Niño events, suggesting an enhanced teleconnection with the low‐latitudes during the late Holocene.

Nanoparticles coated with the tumor-penetrating peptide iRGD reduce experimental breast cancer metastasis in the brain - Amanda M. Hamilton; Sallouha Aidoudi-Ahmed; Shweta Sharma; Venkata R. Kotamraju; Paula J. Foster; Kazuki N. Sugahara; Erkki Ruoslahti; Brian K. Rutt (Journal of Molecular Medicine, 2015)

The paleoclimatic and geochronologic utility of coring red beds and evaporites: a case study from the RKB core (Permian, Kansas, USA) - Gerilyn S. Soreghan; Kathleen C. Benison; Tyler M. Foster; Jay Zambito; Michael J. Soreghan (International Journal of Earth Sciences, 2015)
Drill core is critical for robust and high-resolution reconstructions of Earth’s climate record, as well demonstrated from both marine successions and modern long-lived lake systems. Deep-time climate reconstructions increasingly require core-based data, but some facies, notably red beds and evaporites, have garnered less attention for both paleoclimatic and geochronologic analyses. Here, we highlight studies from the Rebecca K. Bounds (RKB) core, a nearly continuous, >1.6 km drill core extending from the Cretaceous to the Mississippian, recovered from the US Midcontinent by Amoco Production Company in 1988, and serendipitously made available for academic research. Recent research conducted on this core illustrates the potential to recover high-resolution data for geochronologic and climatic reconstructions from both the fine-grained red bed strata, which largely represent paleo-loess deposits, and associated evaporite strata. In this case, availability of core was instrumental for (1) accessing a continuous vertical section that establishes unambiguous superposition key to both magnetostratigraphic and paleoclimatic analyses, and (2) providing pristine sample material from friable, soluble, and/or lithofacies and mineralogical species otherwise poorly preserved in surface exposures. The potential for high-resolution paleoclimatic reconstruction from coring of deep-time loess strata in particular remains severely underutilized.

Novel mutations confirm that COL11A2 is responsible for autosomal recessive non-syndromic hearing loss DFNB53 - Imen Chakchouk; M’hamed Grati; Guney Bademci; Mariem Bensaid; Qi Ma; Amine Chakroun; Joseph Foster; Denise Yan; Duygu Duman; Oscar Diaz-Horta; Abdelmonem Ghorbel; Rahul Mittal; et al. (Molecular Genetics and Genomics, 2015)

An ant–plant by-product mutualism is robust to selective logging of rain forest and conversion to oil palm plantation - Tom M. Fayle; David P. Edwards; William A. Foster; Kalsum M. Yusah; Edgar C. Turner (Oecologia, 2015)

Climate remains an important driver of post‐European vegetation change in the eastern United States - Neil Pederson; Anthony W. D'Amato; James M. Dyer; David R. Foster; David Goldblum; Justin L. Hart; Amy E. Hessl; Louis R. Iverson; Stephen T. Jackson; Dario Martin‐Benito; Brian C. McCarthy; Ryan W. McEwan; et al. (Global Change Biology, 2015)

Dormancy and growth of metastatic breast cancer cells in a bone-like microenvironment - Donna M. Sosnoski; Robert J. Norgard; Cassidy D. Grove; Shelby J. Foster; Andrea M. Mastro (Clinical & Experimental Metastasis, 2015)

Experimentally testing and assessing the predictive power of species assembly rules for tropical canopy ants - Tom M. Fayle; Paul Eggleton; Andrea Manica; Kalsum M. Yusah; William A. Foster (Ecology Letters, 2015)
Understanding how species assemble into communities is a key goal in ecology. However, assembly rules are rarely tested experimentally, and their ability to shape real communities is poorly known. We surveyed a diverse community of epiphyte‐dwelling ants and found that similar‐sized species co‐occurred less often than expected. Laboratory experiments demonstrated that invasion was discouraged by the presence of similarly sized resident species. The size difference for which invasion was less likely was the same as that for which wild species exhibited reduced co‐occurrence. Finally we explored whether our experimentally derived assembly rules could simulate realistic communities. Communities simulated using size‐based species assembly exhibited diversities closer to wild communities than those simulated using size‐independent assembly, with results being sensitive to the combination of rules employed. Hence, species segregation in the wild can be driven by competitive species assembly, and this process is sufficient to generate observed species abundance distributions for tropical epiphyte‐dwelling ants.

Characterization of ANKRD11 mutations in humans and mice related to KBG syndrome - Katherina Walz; Devon Cohen; Paul M. Neilsen; Joseph Foster; Francesco Brancati; Korcan Demir; Richard Fisher; Michelle Moffat; Nienke E. Verbeek; Kathrine Bjørgo; Adriana Lo Castro; Paolo Curatolo; et al. (Human Genetics, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

mGluR5 positive allosteric modulation and its effects on MK-801 induced set-shifting impairments in a rat operant delayed matching/non-matching-to-sample task - Amber L. LaCrosse; Brian T. Burrows; Rachel M. Angulo; Phoebe R. Conrad; Sarah M. Himes; Nordia Mathews; Scott A. Wegner; Sara B. Taylor; M. Foster Olive (Psychopharmacology, 2015)

Contrast-enhanced molecular ultrasound differentiates endoglin genotypes in mouse embryos - J. M. Denbeigh; B. A. Nixon; J. J. Y. Lee; M. Jerkic; P. A. Marsden; M. Letarte; M. C. Puri; F. S. Foster (Angiogenesis, 2015)

Novel life‐history data for threatened seahorses provide insight into fishery effects - J. M. Lawson; S. J. Foster; A. C. O. Lim; V. C. Chong; A. C. J. Vincent (Journal of Fish Biology, 2015)
Life‐history variables for three incidentally captured species of seahorse (Kellogg's seahorse Hippocampus kelloggi , the hedgehog seahorse Hippocampus spinosissimus and the three‐spot seahorse Hippocampus trimaculatus ) were established using specimens obtained from 33 fisheries landing sites in Peninsular Malaysia. When samples were pooled by species across the peninsula, sex ratios were not significantly different from unity, and height and mass relationships were significant for all species. For two of these species, height at physical maturity ( H M ) was smaller than the height at which reproductive activity ( H R ) commenced: H. spinosissimus ( H M = 99·6 mm, H R = 123·2 mm) and H. trimaculatus ( H M = 90·5 mm, H R = 121·8 mm). For H. kelloggi , H M could not be estimated as all individuals were physically mature, while H R = 167·4 mm. It appears that all three Hippocampus spp. were, on average, caught before reproducing; height at 50% capture ( H C ) was ≥ H M but ≤ H R . The results from this study probe the effectiveness of assessment techniques for data‐poor fisheries that rely heavily on estimates of length at maturity, especially if maturity is poorly defined. Findings also question the sustainability of H. trimaculatus catches in the south‐west region of Peninsular Malaysia, where landed specimens had a notably smaller mean height (86·2 mm) and markedly skewed sex ratio (6% males) compared with samples from the south‐east and north‐west of the peninsula.

The influence of bacteria on the arsenic species produced by laboratory cultures of the marine phytoplankton Dunaliella tertiolecta - Elliott G. Duncan; William A. Maher; Simon D. Foster; Katarina M. Mikac; Frank Krikowa (Journal of Applied Phycology, 2014)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Spotted bat (Euderma maculatum) microsatellite discovery using illumina sequencing - Faith M. Walker; Jeffrey T. Foster; Kevin P. Drees; Carol L. Chambers (Conservation Genetics Resources, 2014)

Key flowering genes including FT-like genes are upregulated in the vasculature of apple dwarfing rootstocks - Toshi M. Foster; Amy E. Watson; Ben M. van Hooijdonk; Robert J. Schaffer (Tree Genetics & Genomes, 2014)

Combined antiretroviral therapy reduces brain viral load and pathological features of HIV encephalitis in a mouse model - Rajeth Koneru; M. Foster Olive; William R. Tyor (Journal of NeuroVirology, 2014)

Metal accumulation in the greentail prawn, Metapenaeus bennettae, in Sydney and Port Hacking estuaries, Australia - K. L. M. Lewtas; G. F. Birch; C. Foster-Thorpe (Environmental Science and Pollution Research, 2014)

Metabolic potential of lithifying cyanobacteria-dominated thrombolitic mats - Jennifer M. Mobberley; Christina L. M. Khodadad; Jamie S. Foster (Photosynthesis Research, 2013)

Current known range of the Platte River caddisfly, Ironoquia plattensis, and genetic variability among populations from three Nebraska Rivers - Lindsay A. Vivian; Michael Cavallaro; Kate Kneeland; Erica Lindroth; W. Wyatt Hoback; Kerri M. Farnsworth-Hoback; Robert R. Harms; John E. Foster (Journal of Insect Conservation, 2013)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Genetic diversity and relatedness of the mangrove Rhizophora mangle L. (Rhizophoraceae) using amplified fragment polymorphism (AFLP) among locations in Florida, USA and the Caribbean - M. Albrecht; K. M. Kneeland; E. Lindroth; J. E. Foster (Journal of Coastal Conservation, 2013)

Viral infection of Phaeocystis globosa impedes release of chitinous star‐like structures: quantification using single cell approaches - A. R. Sheik; C. P. D. Brussaard; G. Lavik; R. A. Foster; N. Musat; B. Adam; M. M. M. Kuypers (Environmental Microbiology, 2013)
Summary Phaeocystis globosa is an ecologically important bloom‐forming phytoplankton, which sequesters substantial amounts of inorganic carbon and can form carbon‐enriched chitinous star‐like structures. Viruses infecting P. globosa (PgVs) play a significant regulatory role in population dynamics of the host species. However, the extent to which viruses alter host physiology and its carbon assimilation on single cell level is still largely unknown. This study demonstrates for the first time the impact of viral infection on carbon assimilation and cell morphology of individual axenic P. globosa cells using two single cell techniques: high resolution nanometre‐scale Secondary‐Ion Mass Spectrometry (nanoSIMS) approach and atomic force microscopy (AFM). Up until viral lysis (19 h post infection), the bulk carbon assimilation by infected P. globosa cultures was identical to the assimilation by the non‐infected cultures (33 µmol C l −1 ). However, single cell analysis showed that viral infection of P. globosa impedes the release of star‐like structures. Non‐infected cells transfer up to 44.5 µmol C l −1 (36%) of cellular biomass in the form of star‐like structures, suggesting a vital role in the survival of P. globosa cells. We hypothesize that impediment of star‐like structures in infected P. globosa cells may inactivate viral infectivity by forming flocculants after cell lysis. Moreover, we show that substantial amounts of newly produced viruses (∼ 68%) were attached to P. globosa cells prior to cell lysis. Further, we speculate that infected cells become more susceptible for grazing which provides potential reasons for the sudden disappearance of PgVs in the environment. The scenarios of enhanced grazing is at odds to the current perspective that viral infections facilitates microbial mediated processes by diverting host material away from the higher trophic levels.

Attenuation of reinstatement of methamphetamine-, sucrose-, and food-seeking behavior in rats by fenobam, a metabotropic glutamate receptor 5 negative allosteric modulator - Lucas R. Watterson; Peter R. Kufahl; Natali E. Nemirovsky; Kaveish Sewalia; Lauren E. Hood; M. Foster Olive (Psychopharmacology, 2013)

Targeted genome enrichment for efficient purification of endosymbiont DNA from host DNA - Sandrine Geniez; Jeremy M. Foster; Sanjay Kumar; Bouziane Moumen; Emily LeProust; Owen Hardy; Moraima Guadalupe; Stephen J. Thomas; Braden Boone; Cynthia Hendrickson; Didier Bouchon; Pierre Grève; et al. (Symbiosis, 2012)

The effect of skin temperature on performance during a 7.5-km cycling time trial - Koen Levels; Jos J. de Koning; Carl Foster; Hein A. M. Daanen (European Journal of Applied Physiology, 2012)

Chronic aspiration shifts the immune response from adaptive immunity to innate immunity in a murine model of asthma - Kuei-Ying Su; Anitra D. Thomas; Jui-Chih Chang; Jason H. Leung; Sean M. Lee; Zoie E. Holzknecht; Mary Lou Everett; W. Michael Foster; Monica Kraft; William Parker; R. Duane Davis; Shu S. Lin (Inflammation Research, 2012)

Glaciotectonic deformation associated with the Orient Point–Fishers Island moraine, westernmost Block Island Sound: further evidence of readvance of the Laurentide ice sheet - Lawrence J. Poppe; Robert N. Oldale; David S. Foster; Shepard M. Smith (Geo-Marine Letters, 2012)

Isolation and characterization of eight novel microsatellite loci in endangered Wyoming toad, Bufo baxteri - Renee M. Martin; Connie L. Keeler-Foster; Kenneth G. Boykin; Gerard Zegers; Wade D. Wilson (Conservation Genetics Resources, 2012)

Submarine pyroclastic deposits formed during the 20th May 2006 dome collapse of the Soufrière Hills Volcano, Montserrat - J. Trofimovs; C. Foster; R. S. J. Sparks; S. Loughlin; A. Le Friant; C. Deplus; L. Porritt; T. Christopher; R. Luckett; P. J. Talling; M. R. Palmer; T. Le Bas (Bulletin of Volcanology, 2012)

Comparative microbial diversity analyses of modern marine thrombolitic mats by barcoded pyrosequencing - Jennifer M. Mobberley; Maya C. Ortega; Jamie S. Foster (Environmental Microbiology, 2012)
Summary Thrombolites are unlaminated carbonate structures that form as a result of the metabolic interactions of complex microbial mat communities. Thrombolites have a long geological history; however, little is known regarding the microbes associated with modern structures. In this study, we use a barcoded 16S rRNA gene‐pyrosequencing approach coupled with morphological analysis to assess the bacterial, cyanobacterial and archaeal diversity associated with actively forming thrombolites found in Highborne Cay, Bahamas. Analyses revealed four distinct microbial mat communities referred to as black, beige, pink and button mats on the surfaces of the thrombolites. At a coarse phylogenetic resolution, the domain bacterial sequence libraries from the four mats were similar, with Proteobacteria and Cyanobacteria being the most abundant. At the finer resolution of the rRNA gene sequences, significant differences in community structure were observed, with dramatically different cyanobacterial communities. Of the four mat types, the button mats contained the highest diversity of Cyanobacteria , and were dominated by two sequence clusters with high similarity to the genus Dichothrix, an organism associated with the deposition of carbonate. Archaeal diversity was low, but varied in all mat types, and the archaeal community was predominately composed of members of the Thaumarchaeota and Euryarchaeota . The morphological and genetic data support the hypothesis that the four mat types are distinctive thrombolitic mat communities.

Detecting end-member structural and biological elements of a coral reef using a single-beam acoustic ground discrimination system - Greg Foster; Victor S. Ticzon; Bernhard M. Riegl; Peter J. Mumby (International Journal of Remote Sensing, 2011)

A blended global snow product using visible, passive microwave and scatterometer satellite data - James L. Foster; Dorothy K. Hall; John B. Eylander; George A. Riggs; Son V. Nghiem; Marco Tedesco; Edward Kim; Paul M. Montesano; Richard E. J. Kelly; Kimberly A. Casey; Bhaskar Choudhury (International Journal of Remote Sensing, 2011)

FAP, gastric cancer, and genetic counseling featuring children and young adults: a family study and review - Henry T. Lynch; Carrie Snyder; Janine M. Davies; Stephen Lanspa; Jane Lynch; Zoran Gatalica; Victoria Graeve; Jason Foster (Familial Cancer, 2010)

Hepatocellular hypertrophy and cell proliferation in Sprague–Dawley rats following dietary exposure to ammonium perfluorooctanoate occurs through increased activation of the xenosensor nuclear receptors PPARα and CAR/PXR - Clifford R. Elcombe; Barbara M. Elcombe; John R. Foster; David G. Farrar; Reinhard Jung; Shu-Ching Chang; Gerald L. Kennedy; John L. Butenhoff (Archives of Toxicology, 2010)

Regional differences in awareness and attitudes regarding genetic testing for disease risk and ancestry - Charles R. Jonassaint; Eunice R. Santos; Crystal M. Glover; Perry W. Payne; Grace-Ann Fasaye; Nefertiti Oji-Njideka; Stanley Hooker; Wenndy Hernandez; Morris W. Foster; Rick A. Kittles; Charmaine D. Royal (Human Genetics, 2010)

The Wolbachia endosymbiont as an anti-filarial nematode target - Barton E. Slatko; Mark J. Taylor; Jeremy M. Foster (Symbiosis, 2010)

Damage to the reefs of Port Honduras Marine Reserve, Belize, during the 28 May 2009 earthquake - N. L. Foster; M. Williams; S. Chan; C. Ramirez; V. Vasquez (Coral Reefs, 2010)

A Mechanism for the induction of renal tumours in male Fischer 344 rats by short-chain chlorinated paraffins - Gayathri D. Warnasuriya; Barbara M. Elcombe; John R. Foster; Clifford R. Elcombe (Archives of Toxicology, 2010)

PanTHERIA: a species‐level database of life history, ecology, and geography of extant and recently extinct mammals - Kate E. Jones; Jon Bielby; Marcel Cardillo; Susanne A. Fritz; Justin O'Dell; C. David L. Orme; Kamran Safi; Wes Sechrest; Elizabeth H. Boakes; Chris Carbone; Christina Connolly; Michael J. Cutts; et al. (Ecology, 2009)
Analyses of life‐history, ecological, and geographic trait differences among species, their causes, correlates, and likely consequences are increasingly important for understanding and conserving biodiversity in the face of rapid global change. Assembling multispecies trait data from diverse literature sources into a single comprehensive data set requires detailed consideration of methods to reliably compile data for particular species, and to derive single estimates from multiple sources based on different techniques and definitions. Here we describe PanTHERIA, a species‐level data set compiled for analysis of life history, ecology, and geography of all known extant and recently extinct mammals. PanTHERIA is derived from a database capable of holding multiple geo‐referenced values for variables within a species containing 100 740 lines of biological data for extant and recently extinct mammalian species, collected over a period of three years by 20 individuals. PanTHERIA also includes spatial databases of mammalian geographic ranges and global climatic and anthropogenic variables. Here we detail how the data fields are extracted and defined for PanTHERIA using a customized data input format (MammalForm); how data were collected from the literature, species names and sources tracked, error‐checking and validation procedures applied, and how data were consolidated into species‐level values for each variable. Tables of the consolidated species‐level values are made available for each of two recent species‐level taxonomic classifications of mammals, as well as associated taxonomic synonymy conversion and data‐input files. This study provides a useful guide to prospective researchers on how to structure and codify life‐history, ecological, geographic, and taxonomic data and methods to extract meaningful species‐level traits. It also provides comprehensive information on traits like size, diet, environmental conditions, and ecology to permit macroecological and macroevolutionary analyses of this important clade. The complete data sets corresponding to abstracts published in the Data Papers section of the journal are published electronically in Ecological Archives at 〈 http://esapubs.org/archive 〉. (The accession number for each Data Paper is given directly beneath the title.)

An integrated lake-catchment approach for determining sediment source changes at Aqualate Mere, Central England - Nathan J. Pittam; Ian D. L. Foster; Tim M. Mighall (Journal of Paleolimnology, 2009)

Plasmids captured in C. metallidurans CH34: defining the PromA family of broad-host-range plasmids - Géraldine A. Van der Auwera; Jaroslaw E. Król; Haruo Suzuki; Brian Foster; Rob Van Houdt; Celeste J. Brown; Max Mergeay; Eva M. Top (Antonie van Leeuwenhoek, 2009)

Glucose modulates event-related potential components of recollection and familiarity in healthy adolescents - Michael A. Smith; Leigh M. Riby; Sandra I. Sünram-Lea; J. A. M. van Eekelen; Jonathan K. Foster (Psychopharmacology, 2009)

Role of protein kinase C epsilon (PKCɛ) in the reduction of ethanol reinforcement due to mGluR5 antagonism in the nucleus accumbens shell - Justin T. Gass; M. Foster Olive (Psychopharmacology, 2009)

Stochastic and deterministic processes jointly structure tropical arthropod communities - M. D. Farnon Ellwood; Andrea Manica; William A. Foster (Ecology Letters, 2009)
The question of whether ecological assemblages are structured by stochastic and deterministic (e.g. interspecific competition) processes is controversial, but it is difficult to design sampling regimes and experiments that can dissect the relative importance of stochastic and deterministic processes in natural assemblages. Using null models, we tested communities of arthropod decomposers in tropical epiphytes for patterns of species co‐occurrence, while controlling for habitat gradients, seasonal variations and ecological succession. When environmental conditions were controlled, our analysis showed that the communities were structured stochastically. However, analysing mixed sets of communities that were deliberately created either from two distinct heights or two successional stages revealed that communities were structured deterministically. These results confirm that habitat gradients and dispersal/competition trade‐offs are capable of generating non‐random patterns within decomposer arthropod communities, but reveal that when such effects are accounted for, species co‐occurrence is fundamentally random.

Resistance to race 2 and cross-resistance to race 1 of Kabatiella caulivora in Trifolium subterraneum and T. purpureum - Hua Li; P. G. H. Nichols; S. Han; K. J. Foster; K. Sivasithamparam; M. J. Barbetti (Australasian Plant Pathology, 2009)

Nature of the Weipa Bauxite deposit, northern Australia - G. Taylor; R. A. Eggleton; L. D. Foster; D. B. Tilley; M. Le Gleuher; C. M. Morgan (Australian Journal of Earth Sciences, 2008)

Regolith profile, mineralogy and geochemistry of the Weipa Bauxite, northern Australia - R. A. Eggleton; G. Taylor; M. Le Gleuher; L. D. Foster; D. B. Tilley; C. M. Morgan (Australian Journal of Earth Sciences, 2008)

Landscapes and regolith of Weipa, northern Australia - G. Taylor; R. A. Eggleton; L. D. Foster; C. M. Morgan (Australian Journal of Earth Sciences, 2008)

Using Blood Plasma for Monitoring Organochlorine Contaminants in Juvenile White Sturgeon, Acipenser transmontanus, from the Lower Columbia River - D. T. Gundersen; M. A. H. Webb; A. K. Fink; L. R. Kushner; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck (Bulletin of Environmental Contamination and Toxicology, 2008)

Using multiple archives to understand past and present climate–human–environment interactions: the lake Erhai catchment, Yunnan Province, China - J. A. Dearing; R. T. Jones; J. Shen; X. Yang; J. F. Boyle; G. C. Foster; D. S. Crook; M. J. D. Elvin (Journal of Paleolimnology, 2008)

In vivo deuteration strategies for neutron scattering analysis of bacterial polyhydroxyoctanoate - Robert A. Russell; Peter J. Holden; Karyn L. Wilde; Christopher J. Garvey; Kerie M. Hammerton; L. John R. Foster (European Biophysics Journal, 2008)

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Evidence of local evolution of tomato-infecting begomovirus species in West Africa: characterization of tomato leaf curl Mali virus and tomato yellow leaf crumple virus from Mali - Y.-C. Zhou; M. Noussourou; T. Kon; M. R. Rojas; H. Jiang; L.-F. Chen; K. Gamby; R. Foster; R. L. Gilbertson (Archives of Virology, 2008)

From introduction to fishery dominance: the initial impacts of the invasive carp Cyprinus carpio in Lake Naivasha, Kenya, 1999 to 2006 - J. R. Britton; R. R. Boar; J. Grey; J. Foster; J. Lugonzo; D. M. Harper (Journal of Fish Biology, 2007)
Following the accidental introduction of the carp Cyprinus carpio into Lake Naivasha during 1999, a sustainable population became rapidly established and in early 2004 became the principal species exploited in the commercial fishery. Over 9000 kg of carp were harvested from the lake between October 2005 and 2006, when fish were captured between fork lengths ( L F ) 200 and 800 mm (>8 kg). Diet of carp L F was dominated by zooplankton, >100 mm L F there was a shift to benthic macro‐invertebrates, with these carp feeding principally upon food resources previously unexploited by the fish community. Contrary to predictions and despite the increasing carp abundance, there has been macrophyte regeneration in littoral areas since 2004. There have been substantial increases in areal cover, with coverage in 2006 at levels not observed since the late 1980s, and significant increases in species richness. Possible reasons for this, and the significance of this carp introduction, are discussed.

Acamprosate attenuates cocaine- and cue-induced reinstatement of cocaine-seeking behavior in rats - M. Scott Bowers; Billy T. Chen; Jonathan K. Chou; Megan P. H. Osborne; Justin T. Gass; Ronald E. See; Antonello Bonci; Patricia H. Janak; M. Foster Olive (Psychopharmacology, 2007)

The effect of ambient temperature on gross-efficiency in cycling - Florentina J. Hettinga; Jos J. De Koning; Aukje de Vrijer; Rob C. I. Wüst; Hein A. M. Daanen; Carl Foster (European Journal of Applied Physiology, 2007)

Patient-reporting of side effects may provide an important source of information in clinical practice - Juliet M. Foster; Thys van der Molen; Lolkje de Jong - van den Berg (European Journal of Clinical Pharmacology, 2007)

Molecular genetics of Cicindela (Cylindera) terricola and elevation of C. lunalonga to species level, with comments on its conservation status - M. Ryan Woodcock; Michael G. Kippenhan; C. Barry Knisley; James A. Foster (Conservation Genetics, 2007)

Lamins A and C are present in the nuclei of early porcine embryos, with lamin A being distributed in large intranuclear foci - Helen A. Foster; Paula Stokes; Katherine Forsey; Henry J. Leese; Joanna M. Bridger (Chromosome Research, 2007)

Effects of salinity manipulations on blood pressures in an osmoconforming chordate, the hagfish, Eptatretus cirrhatus - J. M. Foster; M. E. Forster (Journal of Comparative Physiology B, 2006)

Changes in plasma catecholamine concentration during salinity manipulation and anaesthesia in the hagfish Eptatretus cirrhatus - J. M. Foster; M. E. Forster (Journal of Comparative Physiology B, 2006)

EphB3 receptor and ligand expression in the adult rat brain - Christopher A. Willson; Roy D. Foster; Stephen M. Onifer; Scott R. Whittemore; Jorge D. Miranda (Journal of Molecular Histology, 2006)

Incorporation of Plant Residues into Soil Organic Matter Fractions With Grassland Management Practices in the North American Midwest - S. A. Billings; C. M. Brewer; B. L. Foster (Ecosystems, 2006)

Anxiogenic and aversive effects of corticotropin-releasing factor (CRF) in the bed nucleus of the stria terminalis in the rat: role of CRF receptor subtypes - Lacey L. Sahuque; Erika F. Kullberg; Andrew J. Mcgeehan; Jennifer R. Kinder; Megan P. Hicks; Mary G. Blanton; Patricia H. Janak; M. Foster Olive (Psychopharmacology, 2006)

Post-depositional 137Cs Mobility in the Sediments of Three Shallow Coastal Lagoons, SW England - I. D. L. Foster; T. M. Mighall; H. Proffitt; D. E. Walling; P. N. Owens (Journal of Paleolimnology, 2006)

The Definition of British Water Beetle Species Pools (Coleoptera) and their Relationship to Altitude, Temperature, Precipitation and Land Cover Variables - M. D. Eyre; G. N. Foster; M. L. Luff; S. P. Rushton (Hydrobiologia, 2006)

At least one YMHCI molecule in the chicken is alloimmunogenic and dynamically expressed on spleen cells during development - Henry D. Hunt; Ronald M. Goto; Douglas N. Foster; Larry D. Bacon; Marcia M. Miller (Immunogenetics, 2006)

Testing metabolic ecology theory for allometric scaling of tree size, growth and mortality in tropical forests - Helene C. Muller‐Landau; Richard S. Condit; Jerome Chave; Sean C. Thomas; Stephanie A. Bohlman; Sarayudh Bunyavejchewin; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; Kyle E. Harms; Terese Hart; et al. (Ecology Letters, 2006)
The theory of metabolic ecology predicts specific relationships among tree stem diameter, biomass, height, growth and mortality. As demographic rates are important to estimates of carbon fluxes in forests, this theory might offer important insights into the global carbon budget, and deserves careful assessment. We assembled data from 10 old‐growth tropical forests encompassing censuses of 367 ha and > 1.7 million trees to test the theory's predictions. We also developed a set of alternative predictions that retained some assumptions of metabolic ecology while also considering how availability of a key limiting resource, light, changes with tree size. Our results show that there are no universal scaling relationships of growth or mortality with size among trees in tropical forests. Observed patterns were consistent with our alternative model in the one site where we had the data necessary to evaluate it, and were inconsistent with the predictions of metabolic ecology in all forests.

Comparing tropical forest tree size distributions with the predictions of metabolic ecology and equilibrium models - Helene C. Muller‐Landau; Richard S. Condit; Kyle E. Harms; Christian O. Marks; Sean C. Thomas; Sarayudh Bunyavejchewin; George Chuyong; Leonardo Co; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; et al. (Ecology Letters, 2006)
Tropical forests vary substantially in the densities of trees of different sizes and thus in above‐ground biomass and carbon stores. However, these tree size distributions show fundamental similarities suggestive of underlying general principles. The theory of metabolic ecology predicts that tree abundances will scale as the −2 power of diameter. Demographic equilibrium theory explains tree abundances in terms of the scaling of growth and mortality. We use demographic equilibrium theory to derive analytic predictions for tree size distributions corresponding to different growth and mortality functions. We test both sets of predictions using data from 14 large‐scale tropical forest plots encompassing censuses of 473 ha and > 2 million trees. The data are uniformly inconsistent with the predictions of metabolic ecology. In most forests, size distributions are much closer to the predictions of demographic equilibrium, and thus, intersite variation in size distributions is explained partly by intersite variation in growth and mortality.

Modelling the spread of scrapie in a sheep flock: evidence for increased transmission during lambing seasons - S. Touzeau; M. E. Chase-Topping; L. Matthews; D. Lajous; F. Eychenne; N. Hunter; J. D. Foster; G. Simm; J.-M. Elsen; M. E. J. Woolhouse (Archives of Virology, 2006)

Mercury Concentrations in Gonad, Liver, and Muscle of White Sturgeon Acipenser transmontanus in the Lower Columbia River - M. A. H. Webb; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck; M. Plumlee; C. Wong; D. T. Gundersen (Archives of Environmental Contamination and Toxicology, 2006)

Relative contributions of adjacent species set and environmental conditions to plant community richness and composition in a group of created wetlands - Sharon M. Ashworth; Bryan L. Foster; Kelly Kindscher (Wetlands, 2006)

Use of optical density as a measure of Claviceps africana conidial suspension concentration - D. J. Herde; M. J. Ryley; S. D. Foster; V. J. Galea; R. G. Henzell; D. R. Jordan (Australasian Plant Pathology, 2006)

Milk thistle and indinavir: a randomized controlled pharmacokinetics study and meta-analysis - Edward Mills; Kumanan Wilson; Mike Clarke; Brian Foster; Scott Walker; Beth Rachlis; Nick DeGroot; Victor M. Montori; Wayne Gold; Elizabeth Phillips; Stephen Myers; Keith Gallicano (European Journal of Clinical Pharmacology, 2005)

Identification Of Sex Pheromone Components Of The Painted Apple Moth: A Tussock Moth With A Thermally Labile Pheromone Component - A. M. El-Sayed; A. R. Gibb; D. M. Suckling; B. Bunn; S. Fielder; D. Comeskey; L. A. Manning; S. P. Foster; B. D. Morris; T. ando; K. Mori (Journal of Chemical Ecology, 2005)

Ag-ELISA and PCR for Monitoring the Vaccination of Cattle against Taenia saginata Cysticercosis Using an Oncospheral Adhesion Protein (HP6) with Surface and Secreted Localization - L.J.S. Harrison; T. Garate; D.M. Bryce; L.M. Gonzalez; M. Foster-Cuevas; L.W. Wamae; J.A. Onyango-Abuje; R.M.E. Parkhouse (Tropical Animal Health and Production, 2005)

Influence of Targets and Assessment Region Size on Perceived Conservation Priorities - David D. Diamond; C. Diane True; Taisia M. Gordon; Scott P. Sowa; Walter E. Foster; K. Bruce Jones (Environmental Management, 2005)

Heat-shock proteins and their role in chondrocyte protection, an application for autologous transplantation - D. A. Sawatzky; R. Foster; M. P. Seed; D. A. Willoughby (Inflammopharmacology, 2005)

Exploring the relationship between land cover and the distribution of water beetle species (Coleoptera) at the regional scale - M. D. Eyre; G. N. Foster; M. L. Luff (Hydrobiologia, 2005)

The new plant virus family Flexiviridae and assessment of molecular criteria for species demarcation - M. J. Adams; J. F. Antoniw; M. Bar-Joseph; A. A. Brunt; T. Candresse; G. D. Foster; G. P. Martelli; R. G. Milne; S. K. Zavriev; C. M. Fauquet (Archives of Virology, 2004)

U-Pb columbite-tantalite chronology of rare-element pegmatites using TIMS and Laser Ablation-Multi Collector-ICP-MS - S. R. Smith; G. L. Foster; R. L. Romer; A. G. Tindle; S. P. Kelley; S. R. Noble; M. Horstwood; F. W. Breaks (Contributions to Mineralogy and Petrology, 2004)

Virology Division News: The new plant virus family Flexiviridae and assessment of molecular criteria for species demarcation - M. J. Adams; J. F. Antoniw; M. Bar-Joseph; A. A. Brunt; T. Candresse; G. D. Foster; G. P. Martelli; R. G. Milne; C. M. Fauquet (Archives of Virology, 2004)

A high affinity ligand for GABA A -receptor containing a 5 subunit antagonizes ethanol?s neurobehavioral effects in Long-Evans rats - Peter F. McKay; Katrina L. Foster; Dynesha Mason; Shannan McCane; Xiaohui He; Harry L. June; James M. Cook; Rancia Cummings; Marin Garcia; La Shone Williams; Collette Grey (Psychopharmacology, 2004)

Localization and expression of the glutamate transporter, excitatory amino acid transporter 4, within astrocytes of the rat retina - Michelle M. Ward; Theresa Puthussery; Lisa E. Foster; Erica L. Fletcher; Andrew I. Jobling (Cell and Tissue Research, 2004)

Complete nucleotide sequence and analysis of pPSR1 (72,601 bp), a pPT23A-family plasmid from Pseudomonas syringae pv. syringae A2 - G. W. Sundin; C. T. Mayfield; Y. Zhao; T. S. Gunasekera; G. L. Foster; M. S. Ullrich (Molecular Genetics and Genomics, 2004)

An investigation into the relationship between water beetle (Coleoptera) distribution and land cover in Scotland and northeast England - M. D. Eyre; G. N. Foster; M. L. Luff; J. R. Staley (Journal of Biogeography, 2003)
Aims To determine the relationship between satellite‐derived land cover data and distribution patterns of water beetle species pools. Location A total of 687 British national grid 10 km squares in Scotland and 588 1 km grid squares in 99 10 km grid squares in northeast England. Methods Multivariate classification and constrained ordination analyses were used with water beetle species and land cover data. Results The major variation in both the Scotland and northeast England 10 km species pools was from squares with upland acid water habitats to squares with lowland fens and ponds whilst for the 1 km northeast England data it was from squares dominated by fast‐flowing streams and rivers to those with fens and ponds. The secondary variations in the 10 and 1 km analyses were the primary ones juxtaposed. Constrained ordination of the Scottish 10 km data showed upland land cover types to be most influential in determining species pool distribution whilst lowland covers were more important with both the 10 and 1 km northeast England pools. The three analyses showed that coastal cover had a relatively high influence on species pool distribution but no species pool group was dominated by coastal species. Main conclusions There were strong relationships between water beetle species pool distributions and the satellite‐derived land cover types dominating upland and lowland areas. The major variation in the northeast England species pool data differed at the two scales analysed. Results indicated that there is considerable potential for the synthesis of water beetle distribution and land cover data for use in environmental and conservation monitoring at both the regional and national scales.

Comparison of partial sequence of the cap binding protein (eIF4E) isolated from Agaricus bisporus and its pathogen Verticillium fungicola - A.L. Athey-Pollard; M. Kirby; S. Potter; C. Stringer; P.R. Mills; G.D. Foster (Mycopathologia, 2003)

Increase in synthesis of human monoclonal antibodies by transfected Sp2/0 myeloma mouse cell line under conditions of microgravity - L.J.R. Foster; D. Catzel; S. Atwa; M. Zarka; S.M. Mahler (Biotechnology Letters, 2003)

Developmental changes in the functional, biochemical and molecular properties of rat bladder endothelin receptors - Parviz Afiatpour; Jamshid Latifpour; Wataru Takahashi; Makoto Yono; Harris E. Foster; Kazuyoshi Ikeda; Mehdi Pouresmail; Robert M. Weiss (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Changing suspended sediment and particulate phosphorus loads and pathways in underdrained lowland agricultural catchments; Herefordshire and Worcestershire, U.K. - I. D. L. Foster; A. S. Chapman; R. M. Hodgkinson; A. R. Jones; J. A. Lees; S. E. Turner; M. Scott (Hydrobiologia, 2003)

Enhanced hydantoinase and N-carbamoylase activity on immobilisation of Agrobacterium tumefaciens - Ingrid M. Foster; Rosemary D. Dorrington; Stephanie G. Burton (Biotechnology Letters, 2003)

The illusion of preservation: a global environmental argument for the local production of natural resources - Mary M. Berlik; David B. Kittredge; David R. Foster (Journal of Biogeography, 2002)
Aim The United States (US) and other affluent countries consume vast quantities of global natural resources, but contribute proportionately less to the extraction of many raw materials. This imbalance is due, in part, to domestic policies intended to protect the environment. Ironically, developed nations are often better equipped to extract resources in an environmentally prudent manner than the major suppliers. Thus, although citizens of affluent countries may imagine that preservationist domestic policies are conserving resources and protecting nature, heavy consumption rates necessitate resource extraction elsewhere and oftentimes under weak environmental oversight. A major consequence of this ‘illusion of natural resource preservation’ is greater global environmental degradation than would arise if consumption were reduced and a large portion of production was shared by affluent countries. This paper considers some implications of the consumption, management and conservation of forests and wood at a local and global scale. Location We focus on Massachusetts, the eighth most forested state in the USA (by area), the third most densely populated, and an affluent region with consumption rates that are among the highest in the country. Methods Estimates of wood production and consumption are generated, and comparisons are made with other commonly used materials (e.g. steel, concrete, aluminium). Results A comparison of the feasibility and environmental impact of various strategies for dealing with rising wood demand suggests that the US should strive to: (1) reduce per capita consumption of wood and its substitutes, (2) recycle forest products more effectively, (3) protect extensive areas of intensively managed and unmanaged forests and (4) promote sound forest management where the environmental consequences are mild. Forestry and the sustainable generation of wood in Massachusetts would allow preservation of primary forests elsewhere in the world. Main conclusions When aggressive reductions in wood consumption and effective recycling are combined with judiciously increased harvest levels, 50% of the Massachusetts's wood consumption could be met at sustainable rates, even while preserving large undisturbed blocks of forest.

A constitutive gene expression system derived from the tCUP cryptic promoter elements - K. Malik; K. Wu; X.-Q. Li; T. Martin-Heller; M. Hu; E. Foster; L. Tian; C. Wang; K. Ward; M. Jordan; D. Brown; S. Gleddie; et al. (Theoretical and Applied Genetics, 2002)

Island theory, matrix effects and species richness patterns in habitat fragments - William M. Cook; Kurt T Lane; Bryan L. Foster; Robert D. Holt (Ecology Letters, 2002)
Island biogeography theory, created initially to study diversity patterns on islands, is often applied to habitat fragments. A key but largely untested assumption of this application of theory is that landscape matrix species composition is non‐overlapping with that of the islands. We tested this assumption in successional old field patches in a closely mowed matrix, and because our patches are appropriately viewed as sets of contiguous habitat units we studied patterns of species richness per unit area. Previous studies at our site did not find that diversity patterns on patch ‘islands’ conformed to predictions of island biogeography theory. Our results indicate that when matrix species are removed from the patch samples, diversity patterns conform better to theory. We suggest that classical island theory remains an appropriate tool to study diversity patterns in fragmented habitats, but that allowances should be made for spill‐over colonization of ‘islands’ from the ‘sea’.

Improved PCR-based Assays for Pre-symptomatic Diagnosis of Light Leaf Spot and Determination of Mating Type of Pyrenopeziza Brassicae on Winter Oilseed Rape - Simon J. Foster; Alison M. Ashby; Bruce D.L. Fitt (European Journal of Plant Pathology, 2002)

Analysis of candidate antagonists of IAP-mediated caspase inhibition using yeast reconstituted with the mammalian Apaf-1-activated apoptosis mechanism - C. J. Hawkins; J. Silke; A. M. Verhagen; R. Foster; P. G. Ekert; D. M. Ashley (Apoptosis, 2001)

Gonad Organochlorine Concentrations and Plasma Steroid Levels in White Sturgeon ( Acipenser transmontanus ) from the Columbia River, USA - E. P. Foster; M. S. Fitzpatrick; G. W. Feist; C. B. Schreck; J. Yates (Bulletin of Environmental Contamination and Toxicology, 2001)

Plasma Androgen Correlation, EROD Induction, Reduced Condition Factor, and the Occurrence of Organochlorine Pollutants in Reproductively Immature White Sturgeon ( Acipenser transmontanus ) from the Columbia River, USA - E. P. Foster, M. S. Fitzpatrick, G. W. (Archives of Environmental Contamination and Toxicology, 2001)

Enhancers and core promoter elements are essential for the activity of a cryptic gene activation sequence from tobacco, tCUP - K. Wu; K. Malik; L. Tian; M. Hu; T. Martin; E. Foster; D. Brown; B. Miki (Molecular Genetics and Genomics, 2001)

Statistical Analysis of Spatial Pattern: A Comparison of Grid and Hierarchical Sampling Approaches - R. G. Cole; T. R. Healy; M. L. Wood; D. M. Foster (Environmental Monitoring and Assessment, 2001)

Population dynamics of a scrapie outbreak - L. Matthews; P. G. Coen; J. D. Foster; N. Hunter; M. E. J. Woolhouse (Archives of Virology, 2001)

The discriminative stimulus properties of self-administered ethanol are mediated by GABA A and NMDA receptors in rats - Clyde W. Hodge; Amy A. Cox; Alison M. Bratt; Rosana Camarini; Kimberly Iller; Stephen P. Kelley; Kristin K. Mehmert; Michelle A. Nannini; M. Foster Olive (Psychopharmacology, 2001)

Heterogeneity of RMA-S cell line: derivatives of RMA-S cells lacking H2-K b and H2-D b expression - Dewey Howell; Jonathan M. Levitt; Patricia A. Foster; Margaretha M. Guenther; Said M. Shawar; Robert R. Rich; John R. Rodgers (Immunogenetics, 2000)

Analysis of the Structure and Electrophysiological Actions of Halitoxins: 1,3 Alkyl-pyridinium Salts from Callyspongia ridleyi - R.H. Scott; A.D. Whyment; A. Foster; K.H. Gordon; B.F. Milne; M. Jaspars (The Journal of Membrane Biology, 2000)

Expression of endothelin receptor subtypes and their messenger RNAs in diabetic rat prostate: Effect of insulin treatment - Motoaki Saito; Yoshihiro Wado; Kazuyoshi Ikeda; ZeJing Wang; Harris E. Foster; Shannon D. Smith; Robert M. Weiss; Jamshid Latifpour (Molecular and Cellular Biochemistry, 2000)

Molecular characterization of a new member of the immunoglobulin superfamily that potentially functions in T-cell activation and development - D. M. Ruble; D. N. Foster (Immunogenetics, 2000)

Diverse endogenous light chains contribute to basement membrane reactivity in nonautoimmune mice transgenic for an anti-laminin Ig heavy chain - M. M. Fitzsimons; H. Chen; M. H. Foster (Immunogenetics, 2000)

Adaptive response to cold temperatures and characterization of cspA in Salmonella typhimurium LT2 - Amanda J. Horton; Karla M. Hak; Robert J. Steffan; John W. Foster; Asim K. Bej (Antonie van Leeuwenhoek, 2000)

Chemical Stimuli from Apple Influence the Behavior of Neonate Caterpillars of the Generalist Herbivore, Epiphyas postvittana - M. O. Harris; M. Sandanayake; S. P. Foster (Journal of Chemical Ecology, 1999)

Effect of diet on growth rate and reproductive fitness of Turbo sarmaticus (Mollusca: Vetigastropoda: Turbinidae) - G. G. Foster; A. N. Hodgson; M. Balarin (Marine Biology, 1999)

Analysis of a translational enhancer present within the 5′-terminal sequence of the genomic RNA of potato virus S - R. L. Turner; M. Glynn; S. C. Taylor; M.-K. Cheung; C. Spurr; D. Twell; G. D. Foster (Archives of Virology, 1999)

Tetrodotoxin suppresses morphological enhancement of the metastatic MAT-LyLu rat prostate cancer cell line - S. P. Fraser; Y. Ding; A. Liu; C. S. Foster; M. B. A. Djamgoz (Cell and Tissue Research, 1999)

Peptide Growth Factors and Prostate Cancer: New Models, New Opportunities - Barbara A. Foster; Paula J. Kaplan; Norman M. Greenberg (Cancer and Metastasis Reviews, 1998)

Repeated heroin administration increases extracellular opioid peptide-like immunoreactivity in the globus pallidus/ventral pallidum of freely moving rats - M. Foster Olive; N. T. Maidment (Psychopharmacology, 1998)

Nodulation response of woody Papilionoid species after inoculation with rhizobia and soil from Hawaii, Asia and North America - Carol M. Foster; Harry T. Horner; William R. Graves (Plant and Soil, 1998)

Exclusion of a p53 germline mutation in a classic Li-Fraumeni syndrome family - Susan C. Evans; Betsy Mims; Kelly M. McMasters; Carolyn J. Foster; Mariza deAndrade; Christopher I. Amos; Louise C. Strong; Guillermina Lozano (Human Genetics, 1998)

Growth, Survival and Characterization of cspA in Salmonella enteritidis Following Cold Shock - Amanda G. Jeffreys; Karla M. Hak; Robert J. Steffan; John W. Foster; Asim K. Bej (Current Microbiology, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

An immunocytochemical study of encephalic photoreceptors in three species of lamprey - J. M. García-Fernández; A. J. Jiménez; B. González; M. A. Pombal; R. G. Foster (Cell and Tissue Research, 1997)

A CaMV 35S promoter driven cDNA clone of tobacco mosaic virus can infect host plant tissue despite being uninfectious when manually inoculated onto leaves - E. M. Dagless; M. H. Shintaku; R. S. Nelson; G. D. Foster (Archives of Virology, 1997)

Natural scrapie in a closed flock of Cheviot sheep occurs only in specific PrP genotypes - N. Hunter; J. D. Foster; W. Goldmann; M. J. Stear; J. Hope; C. Bostock (Archives of Virology, 1996)

Nephrotoxicity of 4-amino-3-S-glutathionylphenol and its modulation by metabolism or transport inhibitors - Lynn M. Fowler; John R. Foster; Edward A. Lock (Archives of Toxicology, 1994)

Effect of ascorbic acid, acivicin and probenecid on the nephrotoxicity of 4-aminophenol in the Fischer 344 rat - Lynn M. Fowler; John R. Foster; Edward A. Lock (Archives of Toxicology, 1993)

Peroxisome proliferation due to di (2-ethylhexyl) adipate, 2-ethylhexanol and 2-ethylhexanoic acid - Y. Keith; M. C. Cornu; P. M. Canning; J. Foster; J. C. Lhuguenot; C. R. Elcombe (Archives of Toxicology, 1992)

Comparison of rectangular and exponential current pulses for evoking sensation - Jerry L. Wessale; Leslie A. Geddes; Gregory M. Ayers; Kirk S. Foster (Annals of Biomedical Engineering, 1992)

Effects of stage of colony cycle, context, and intercolony distance on conspecific tolerance by paper wasps (Polistes fuscatus) - George J. Gamboa; Robin L. Foster; Julie A. Scope; Angela M. Bitterman (Behavioral Ecology and Sociobiology, 1991)

Almost equivalence of combinatorial and distance processes for discrimination in multielement images - M. Ferraro; D. H. Foster (Biological Cybernetics, 1991)

Genetic studies of Staphylococcus aureus virulence factors - T. J. Foster; M. O'Reilly; A. H. Patel; A. J. Bramley (Antonie van Leeuwenhoek, 1988)

Alcohol dehydrogenase isozymes in grain sorghum (Sorghum bicolor): Evidence for a gene duplication - Norman C. Ellstrand; Janet M. Lee; Ken W. Foster (Biochemical Genetics, 1983)

Residue dynamics and biological effects of polychlorinated biphenyls in aquatic organisms - Foster L. Mayer; Paul M. Mehrle; Herman O. Sanders (Archives of Environmental Contamination and Toxicology, 1977)